Optical laminate and image display device
Patent Information
- Application Number
- CN202411724074.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2016-05-27
- Filing Date
- 2017-05-18
- Publication Date
- 2025-01-24
AI Technical Summary
[0009]但是,这种硬涂膜虽然以某种程度具备优异的硬度和弯曲性,但很难说是充分的
[0330]本发明的层叠体由于由上述构成形成,因而具有极其优异的硬度和耐久折叠性能。
Smart Images

Figure CN119348268A_ABST
Abstract
Description
[0001] This application is a divisional application of the Chinese invention patent application with the application date of May 18, 2017, the invention name of which is “Optical laminate and image display device” and the application number is 201780044632.X. Technical Field
[0002] The present invention relates to an optical layered body and an image display device using the optical layered body. Background Art
[0003] The image display screen in the image display device is required to be scratch-resistant in order to prevent it from being damaged during operation. For this purpose, a hard coating film having a hard coating (HC) layer formed on a substrate film is generally used to improve the scratch resistance of the image display screen of the image display device.
[0004] In recent years, the performance required of such hard coatings has been increasingly improved, and further improvement in hardness and scratch resistance has been required. As a hard coating having excellent hardness and scratch resistance, for example, Patent Document 1 discloses a hard coating having a hard coating layer containing irregular silica particles, an acrylic polymer, and a matrix resin formed on a substrate composed of three or more resin layers.
[0005] Furthermore, in recent years, hard coat films have been required to have, in addition to excellent hardness and scratch resistance, excellent foldability such that cracks do not occur even when the hard coat films are folded repeatedly.
[0006] Furthermore, since the display screen of the image display device needs to be formed not only in a flat plane but also in various curved surfaces, the hard coat film is also required to have excellent bendability so that cracks are not generated even when the hard coat film is formed in a curved surface.
[0007] However, hardness and scratch resistance are usually in a trade-off relationship with foldability and bendability. Therefore, in the case of existing hard coatings, if the hardness and scratch resistance are improved, the foldability and bendability are reduced; if the foldability and bendability are improved, the hardness and scratch resistance are reduced, and these properties cannot be improved at the same time.
[0008] For example, Patent Document 2 discloses a hard coating film having hard coating properties and bendability, wherein two hard coating layers having different Vickers hardnesses are provided on one surface of a transparent substrate.
[0009] However, although such a hard coating film has excellent hardness and flexibility to a certain extent, it can hardly be said that it is sufficient.
[0010] Prior art literature
[0011] Patent Literature
[0012] Patent Document 1: Japanese Patent Application Publication No. 2014-238614
[0013] Patent Document 2: Japanese Patent Application Publication No. 2014-186210 Summary of the invention
[0014] Problems to be solved by the invention
[0015] In view of the above-mentioned current situation, an object of the present invention is to provide a laminate having extremely excellent hardness and folding performance and excellent transparency and surface smoothness; and an image display device using the laminate.
[0016] Means for solving problems
[0017] The present invention relates to a laminated body used in an image display device, the laminated body having a composite substrate film, the composite substrate film having a structure in which a first substrate film and a second substrate film are laminated, the laminated body being characterized in that at least one of the first substrate film and the second substrate film is a polyimide film, a polyamide-imide film, or an aromatic polyamide film, and the laminated body is subjected to a test of being folded 180° with a spacing of 3 mm between two opposing sides repeatedly for 100,000 times, and no cracks or breaks are generated in the laminated body.
[0018] The yellowness index of the laminate of the present invention is preferably 15 or less, and the Young's modulus is preferably 3 GPa or more.
[0019] In addition, the maximum profile height Rz of any area of 5μm×5μm on the surface of the above-mentioned composite substrate film is preferably less than 0.1μm; preferably, when the laminate of the present invention is folded 180° with a spacing of 3mm between two opposing sides and maintained at a temperature of 60°C and a humidity of 90% for 12 hours, the above-mentioned laminate does not produce cracks or breaks.
[0020] In addition, it is preferred that the laminate of the present invention is provided with an optical functional layer on one surface of the above-mentioned composite substrate film, and the bonding strength of the above-mentioned composite substrate film provided with the above-mentioned optical functional layer is greater than 10N / 25mm; in addition, it is preferred that when an iron ball weighing 100g and having a diameter of 30mm is dropped from a height of 30cm on one surface of the laminate of the present invention, the above-mentioned laminate does not generate cracks.
[0021] Furthermore, an image display device including the laminate of the present invention is also one of the present invention.
[0022] Hereinafter, the present invention will be described in detail.
[0023] The inventors of the present invention have conducted in-depth research and found that organic films have the characteristics of being more flexible, less prone to cracking, and lighter than glass substrates. Based on this understanding, organic films are used to form substrate films such as hard coating films of image display devices, especially by using substrate films composed of polyimide films, polyamide-imide films, and aromatic polyamide films, a laminate with excellent folding performance and strength can be obtained.
[0024] Here, polyimide films and the like have problems such as low transmittance in the visible light region due to the high aromaticity of the resin composition and a strong yellow color of the transmitted light.
[0025] For this coloring problem, for example, a method of introducing fluorine atoms into a polyimide film is known. However, when fluorine atoms are introduced into a polyimide film, the barrier properties are reduced due to a decrease in electron density, and mechanical properties such as durability may be impaired.
[0026] In addition, for example, a method of eliminating the yellow coloration of the polyimide film by using the color of another layer to suppress the coloration of the entire film is also known. However, in recent years, image display devices are required to have a higher level of light transmittance and transparency, and as a result, the above method has the problem of reduced light transmittance.
[0027] In view of the above-mentioned situation, the inventors conducted further in-depth research and found that in a laminate used for an image display device, by making the base film a composite base film having at least a first base film and a second base film, and making at least one of the first base film and the second base film a polyimide film, etc., it is possible to obtain a laminate that is excellent in surface smoothness while being able to suppress the above-mentioned coloring problem, thereby completing the present invention.
[0028] Compared with the existing substrate film composed of a single material, this composite substrate film is a laminated first substrate film and a second substrate film as thin films. Therefore, even if at least one of the first substrate film and the second substrate film uses a polyimide film, etc., the occurrence of coloration can be suppressed. Furthermore, since the first substrate film and the second substrate film are thin films, the smoothness of these surfaces can be highly controlled.
[0029] The laminated body of the present invention includes a composite base film having a structure in which a first base film and a second base film are laminated.
[0030] At least one of the first substrate film and the second substrate film constituting the composite substrate film is a polyimide film, a polyamideimide film, or an aromatic polyamide film.
[0031] When at least one of the first base film and the second base film is a polyimide film or the like, the laminate of the present invention has excellent hardness and folding performance.
[0032] In addition, in the above-mentioned composite base film, the first base film and the second base film may both be the above-mentioned polyimide film or the like, or either one of them may be the above-mentioned polyimide film or the like.
[0033] As the first substrate film or the second substrate film other than the polyimide film, for example, polyethylene terephthalate film, triacetyl cellulose film, polyethylene naphthalate film, polyetherimide film, polyether ketone film, (meth)acrylic film, or aromatic polyamide film is preferably used.
[0034] Here, as described above, polyimide films and the like are usually colored (yellow) because they have aromatic rings in the molecule, so films called "transparent polyimide" and "transparent aromatic polyamide" whose transparency is improved by changing the skeleton in the above-mentioned molecule can also be used. However, "transparent polyimide" and the like are expensive materials, so the use of these transparent materials will increase the manufacturing cost.
[0035] On the other hand, the laminate of the present invention can suppress yellow coloration as described above, so it is not necessary to use expensive materials such as transparent polyimide, and it is also possible to prevent an increase in production cost.
[0036] The first substrate film and the second substrate film (hereinafter, both are collectively referred to as "substrate films") preferably have a thickness of 10 μm to 100 μm. If the thickness of the substrate film is less than 10 μm, the curl of the laminate of the present invention becomes larger, and the hardness becomes insufficient, and the pencil hardness described later sometimes becomes insufficient, and further, when the laminate of the present invention is manufactured by a roll-to-roll method, wrinkles are easily generated, which may cause a deterioration in appearance. On the other hand, if the thickness of the substrate film exceeds 100 μm, the folding performance of the laminate of the present invention becomes insufficient, and sometimes the conditions of the durable folding test described later cannot be met, and the laminate of the present invention becomes heavy, which is not preferred in terms of lightweighting.
[0037] Since the laminated body of the present invention has the above-mentioned structure, it has extremely excellent hardness and foldability, and is used in image display devices.
[0038] When the laminate of the present invention was repeatedly folded 180 degrees with the interval between two opposing sides being 3 mm for 100,000 times, the laminate did not crack or break. This condition indicates that the laminate of the present invention has durable folding performance.
[0039] Figure 1 This is a cross-sectional view schematically showing a test (hereinafter also referred to as a durable folding test) in which the laminate of the present invention is folded 180 degrees so that the interval between two opposing sides is 3 mm under the above-mentioned conditions.
[0040] like Figure 1 As shown in (a), in the above-mentioned durable folding test, first, one side of the laminate 10 of the present invention and the other side facing the one side are fixed by parallel fixed parts 11. It should be noted that the laminate of the present invention can be of any shape, but the laminate 10 of the present invention in the above-mentioned durable folding test is preferably a rectangle (for example, a rectangle of 30 mm×100 mm).
[0041] In addition, if Figure 1 As shown, the fixing portion 11 can slide and move in the horizontal direction.
[0042] Then, if Figure 1 As shown in (b), the fixing parts 11 are moved in a manner close to each other, thereby deforming the laminate 10 of the present invention in a folded manner, and then as shown in Figure 1 As shown in (c), the fixing part 11 is moved to a position where the interval between the two opposing sides of the laminate 10 of the present invention fixed by the fixing part 11 reaches 3 mm, and then the fixing part 11 is moved in the reverse direction to release the deformation of the laminate 10 of the present invention. It should be noted that when the laminate 10 of the present invention has an optical functional layer described later, it is folded toward the optical functional layer side (folded in such a way that the surface (back side) opposite to the optical functional layer side becomes the outside).
[0043] Through Figure 1 By moving the fixing portion 11 as shown in (a) to (c), the laminate of the present invention can be folded 180°, and a durability folding test is performed in a manner such that the bent portion 12 of the laminate 10 of the present invention does not protrude from the lower end of the fixing portion 11, and the interval when the fixing portions 11 are closest is controlled to 3 mm, thereby enabling the interval between the two opposing sides of the laminate 10 of the present invention to be 3 mm. In addition, in this case, the outer diameter of the bent portion 12 is regarded as 3 mm ( Figure 1 (c)). It should be noted that the thickness of the laminate of the present invention is sufficiently small compared to the interval (3 mm) of the fixing portion 11, and therefore, the result of the durable folding test of the laminate of the present invention can be considered to be unaffected by the thickness difference of the laminate of the present invention.
[0044] The present invention shows that after performing the above 100,000 times Figure 1 In the case of the folding test shown in (a) to (c) of the present invention, the laminate of the present invention does not produce cracks, etc. If the laminate 10 of the present invention produces cracks, etc. within 100,000 times, the durable folding performance of the laminate of the present invention is insufficient. In the present invention, it is preferred that no cracks, etc., are produced when the above-mentioned durable folding test is performed 150,000 times.
[0045] In the present invention, even when the laminated body 10 of the present invention described above was rotated 90 degrees and subjected to the same endurance folding test, cracks and the like were not generated.
[0046] The laminate of the present invention preferably does not produce cracks or breaks when it is folded at 180° with the interval between the two opposing sides being 3 mm and kept at a temperature of 60°C and a humidity of 90% for 12 hours (hereinafter also referred to as a folding holding test). Figure 1 The state shown in (c) did not cause cracks or breaks when the temperature was kept at 60° C. and the humidity was kept at 90% for 12 hours.
[0047] The durable folding test shows the strength of the laminate of the present invention when it is repeatedly folded, and the folding retention test shows the strength of the laminate of the present invention when it is stored in a folded state for a long period of time under a high temperature and high humidity environment.
[0048] In addition, the laminate of the present invention having the above-mentioned structure has excellent transparency because it includes the first base film and the second base film which are thin films and whose coloring is suppressed as a composite base film as described above.
[0049] Specifically, the yellow index (YI) of the laminate of the present invention is preferably 15 or less. If the YI exceeds 15, the yellow color of the laminate of the present invention is conspicuous, and the laminate of the present invention may not be used for applications requiring transparency. A more preferred upper limit of the YI is 10.
[0050] It should be noted that the above-mentioned YI is a value calculated as follows: using a spectrophotometer (product name "UV-3100PC", manufactured by Shimadzu Corporation, light source: tungsten lamp and deuterium lamp), the laminate of the present invention cut into a size of 5 cm×10 cm is measured, and the chromaticity tristimulus values X, Y, and Z are calculated from the measured values according to the calculation formula described in JIS Z8722:2009, and YI is calculated from the calculated tristimulus values X, Y, and Z according to the calculation formula described in ASTM D1925:1962.
[0051] In addition, in order to adjust the yellow index (YI) of the laminate of the present invention, for example, a blue pigment as a complementary color of yellow may be contained in the composite substrate film or in any layer on the composite substrate film. By using a polyimide film as the composite substrate film, even if yellow coloring becomes a problem, the YI of the laminate of the present invention can be suppressed by including the blue pigment.
[0052] The blue coloring matter may be any of a pigment and a dye. For example, when the laminate of the present invention is used in an organic electroluminescent display device, it is preferred that the blue coloring matter has both light resistance and heat resistance.
[0053] As the above-mentioned blue pigment, polycyclic organic pigments, metal complex organic pigments, etc. have less molecular breakage caused by ultraviolet rays than molecular dispersion of dyes and are particularly excellent in light resistance, so they are preferably used for applications requiring light resistance, etc. More specifically, phthalocyanine-based organic pigments and the like are preferably used.
[0054] Yet, because pigment is dispersed in the solvent, there is the transparency that is caused by particle scattering, so preferably make the particle size of pigment dispersion in Rayleigh scattering region.On the other hand, when paying attention to the transparency of laminated body of the present invention, as above-mentioned blue pigment, preferably use the dyestuff that molecular dispersion takes place in the solvent.
[0055] The Young's modulus of the laminate of the present invention is preferably 3 GPa or more. If it is less than 3 GPa, the hardness of the laminate of the present invention becomes insufficient. For example, when the laminate of the present invention is used in a mobile terminal such as a smart phone or a tablet terminal and is impacted by falling, cracks or breaks may occur. A more preferred lower limit of the Young's modulus is 4 GPa, and a further preferred lower limit is 5 GPa.
[0056] It should be noted that the above-mentioned Young's modulus is a value obtained as follows: using a Tensilon universal testing machine (RTC-1310A, manufactured by ORIENTEC), the two ends of the stack cut into 2 mm×50 mm are fixed to a clamping fixture attached to the Tensilon universal testing machine in such a way that the length direction is the tensile direction, and the measured values of the elongation and load of the stack when stretched at a test speed of 25 mm / min are converted into strain and stress, and the slope of the straight line formed by the strain and stress is calculated in the area where the relationship between the strain and stress is linear, thereby obtaining the Young's modulus.
[0057] Since the laminate of the present invention has a structure having the above-mentioned composite substrate film, when an iron ball weighing 100g and having a diameter of 30mm is dropped from a height of 30cm on one surface of the laminate of the present invention (hereinafter also referred to as a drop ball test), it is preferred that the laminate does not produce cracks. The drop ball test is performed as follows: a soda-lime glass having a thickness of 0.7mm is placed on a flat table, the laminate of the present invention is cut into a size of 5cm×15cm to obtain a sample, the obtained sample is fixed to the soda-lime glass using CELLOTAPE (registered trademark) manufactured by Michelbon in a manner without folding or wrinkling, and the drop ball test is performed in this state. If cracks or the like are generated in such a drop ball test, the strength of the laminate of the present invention may sometimes become insufficient.
[0058] The laminate of the present invention having such excellent strength preferably includes a hard coating layer described below.
[0059] In addition, the surface smoothness of the laminate of the present invention having the above structure is excellent, and the maximum height Rz of the profile of any area of 5 μm×5 μm on the surface of the composite substrate film is preferably 0.1 μm or less. It should be noted that the maximum height Rz of the profile is measured in accordance with JIS B0601:2001 using a scanning probe microscope (SPM-9600, manufactured by Shimadzu Corporation). If the maximum height Rz of the profile exceeds 0.1 μm, the smoothness of the laminate of the present invention may become insufficient.
[0060] A more preferred upper limit of the profile maximum height Rz is 0.09 μm, and a further preferred upper limit is 0.08 μm.
[0061] Such a composite substrate film may be formed by, for example, simultaneously laminating a first substrate film and a second substrate film by a co-extrusion method, or may be formed by separately forming the first substrate film and the second substrate film and laminating them via an adhesive layer or a bonding layer.
[0062] Alternatively, the third base film and the fourth base film may be formed separately and laminated on the first base film and the second base film via an adhesive layer or a bonding layer.
[0063] Among them, a structure in which a first base film and a second base film are bonded together via an adhesive layer is preferred.
[0064] The adhesive layer is not particularly limited, and various known adhesives such as ultraviolet curing resins and thermosetting resins can be widely used. Among them, ultraviolet curing resins are preferably used.
[0065] As such an ultraviolet curable resin, for example, a monofunctional acrylic monomer is preferably used.
[0066] The monofunctional acrylic monomer is preferably at least one selected from the group consisting of acryloylmorpholine, N-acryloyloxyethylhexahydrophthalimide, cyclohexyl acrylate, tetrahydrofuran acrylate, isobornyl acrylate, phenoxyethyl acrylate and adamantyl acrylate. Among them, acryloylmorpholine is preferred because, when a polyimide film having excellent solvent resistance is used as a composite substrate film, the film can be well dissolved and extremely excellent interference fringe prevention performance can be imparted.
[0067] The adhesive layer using the monofunctional monomer can be formed, for example, by applying an adhesive layer composition of a monofunctional monomer containing the monofunctional monomer and a solvent onto one surface of the first substrate film, and then drying and curing the formed coating.
[0068] As the solvent in the adhesive layer composition of the monofunctional monomer, the solvent used in the hard coat layer composition described later can be preferably used.
[0069] The adhesive layer composition of the above-mentioned monofunctional monomer can be added with a photopolymerization initiator, a dispersant, a surfactant, an antistatic agent, a silane coupling agent, a thickener, an anti-coloring agent, a colorant (pigment, dye), a defoaming agent, a leveling agent, a flame retardant, an ultraviolet absorber, an adhesion-imparting agent, an inhibitor, an antioxidant, a surface modifier, etc., in the same manner as the hard coating composition described later.
[0070] In addition, when acrylamide morpholine (ACMO) is used as the monofunctional monomer used in the adhesive layer of the above-mentioned monofunctional monomer, the water resistance of the cured layer (adhesive layer) is sometimes poor. Therefore, assuming that it is used outdoors or in a high-humidity environment, instead of the cured layer of the above-mentioned ACMO, it is preferred to use a monomer with excellent water resistance as a material (low moisture permeability material) to form an adhesive layer (also referred to as a water-resistant adhesive layer) as the above-mentioned adhesive layer. It should be noted that, for example, the cured layer (ACMO layer) of the above-mentioned ACMO can contain the above-mentioned low moisture permeability material, and a layer of low moisture permeability material can also be provided on at least one surface of the ACMO layer.
[0071] The water-resistant adhesive layer is not particularly limited, and examples thereof include an adhesive layer formed by curing a curable composition containing at least one of a compound having a cyclic aliphatic hydrocarbon group and an ethylenically unsaturated double bond, and a compound having a fluorene ring and an ethylenically unsaturated double bond as a low moisture permeability material.
[0072] The cyclic aliphatic hydrocarbon group is preferably a group having 7 or more carbon atoms derived from an alicyclic compound, more preferably a group having 10 or more carbon atoms derived from an alicyclic compound, and still more preferably a group having 12 or more carbon atoms derived from an alicyclic compound.
[0073] As the cyclic aliphatic hydrocarbon group, a group derived from a polycyclic compound such as a bicyclic compound or a tricyclic compound is more preferred.
[0074] Particularly preferred examples of the cyclic aliphatic hydrocarbon group include the central skeleton of a compound represented by the following formula (1), the central skeleton of a compound represented by the following formula (2), and the skeleton of an adamantane derivative.
[0075]
Chemistry 1
[0076]
[0077]
Chemistry 2
[0078]
[0079] It should be noted that in formulas (1) and (2), R 1 represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, and n represents an integer of 1 or 2.
[0080] Specific examples of the cyclic aliphatic hydrocarbon group include norbornyl, tricyclodecanyl, tetracyclododecyl, pentacyclopentadecyl, adamantyl, and bisadamantyl.
[0081] In addition, as the above-mentioned cyclic aliphatic hydrocarbon group (including the linking group), a group represented by any one of the following general formulas (I) to (V) is preferred, a group represented by the following general formula (I), (II) or (IV) is more preferred, and a group represented by the following general formula (I) or (IV) is further preferred.
[0082]
Chemistry 3
[0083]
[0084] In the general formula (I), L and L1 each independently represent a single bond or a divalent or higher valent linking group. n represents an integer of 1-3.
[0085]
Chemistry 4
[0086]
[0087] In the general formula (II), L and L1 each independently represent a single bond or a divalent or higher valent linking group. n represents an integer of 1-2.
[0088]
Chemistry 5
[0089]
[0090] In the general formula (III), L and L1 each independently represent a single bond or a divalent or higher valent linking group. n represents an integer of 1-2.
[0091]
Chemistry 6
[0092]
[0093] In the general formula (IV), L and L1 each independently represent a single bond or a divalent or higher-valent linking group, and L2 represents a hydrogen atom, a single bond or a divalent or higher-valent linking group.
[0094]
Chemistry 7
[0095]
[0096] In the general formula (V), L and L1 each independently represent a single bond or a divalent or higher linking group. Examples of divalent or higher linking groups of L and L1 include an alkylene group having 1 to 6 carbon atoms which may be substituted, an amide bond which may be substituted at the N position, a carbamate bond which may be substituted at the N position, an ester bond, an oxycarbonyl group, an ether bond, and a group obtained by combining two or more of these.
[0097] As the above-mentioned ethylenically unsaturated double bond, for example, polymerizable functional groups such as (meth)acryloyl, vinyl, styryl, and allyl can be cited, among which (meth)acryloyl and -C(O)OCH=CH2 are preferred. More preferred are compounds containing two or more (meth)acryloyl groups in one molecule as exemplified in the following M-1 to M-4.
[0098] The compound having a cyclic aliphatic hydrocarbon group and having two or more ethylenically unsaturated double bonds in the molecule is composed of the cyclic aliphatic hydrocarbon group and the group having an ethylenically unsaturated double bond linked via a linking group.
[0099] These compounds can be easily synthesized, for example, by reacting a polyol such as a diol or triol having the above-mentioned cyclic aliphatic hydrocarbon group with a carboxylic acid, a carboxylic acid derivative, an epoxy derivative, an isocyanate derivative, or the like of a compound having a (meth)acryloyl group, a vinyl group, a styryl group, an allyl group, or the like in a single or two-step reaction.
[0100] Preferably, it can be synthesized by reacting a compound such as (meth)acrylic acid, (meth)acryloyl chloride, (meth)acrylic anhydride, glycidyl (meth)acrylate, or a compound described in WO2012 / 00316A (e.g., 1,1-bis(acryloyloxymethyl)ethyl isocyanate) with a polyol having the above-mentioned cyclic aliphatic hydrocarbon group.
[0101] The compound having a cyclic aliphatic hydrocarbon group and having an ethylenically unsaturated double bond is not particularly limited, and examples thereof include compounds represented by the following M-1 to M-6.
[0102]
Chemistry 8
[0103]
[0104]
Chemistry 9
[0105]
[0106] In addition, in order to increase the crosslinking point density, the compound having a fluorene ring and an ethylenically unsaturated double bond preferably has two or more ethylenically unsaturated double bonds in the molecule.
[0107] As the compound having a fluorene ring and an ethylenically unsaturated double bond, for example, a compound represented by the following general formula (VI) is preferred.
[0108]
Chemistry 10
[0109]
[0110] In formula (VI), R 3 , R 4 , R 5 , R 6 , R 7 and R 8 Each independently represents a monovalent substituent, m, n, p and q each independently represent an integer of 0 to 4, R 3 and R 4 At least one of represents a monovalent organic group having an ethylenically unsaturated double bond.
[0111] As a preferred embodiment of the compound represented by the above general formula (VI) which has a fluorene skeleton and an ethylenically unsaturated double bond in the molecule, there can be mentioned, for example, a compound represented by the following general formula (VII).
[0112]
Chemistry 11
[0113]
[0114] In the above formula (VII), R 9 , R 10 represents hydrogen or methyl, and r and s represent integers of 0-5.
[0115] When the total solid content of the curable composition for forming the second layer is set to 100% by mass, the content of at least any one of the compound having a cyclic aliphatic hydrocarbon group and an ethylenically unsaturated double bond and the compound having a fluorene ring and an ethylenically unsaturated double bond is preferably 50 to 99% by mass, and from the perspective of significant reduction in moisture permeability, it is more preferably more than 50% by mass and not more than 99% by mass, further preferably 55 to 95% by mass, and particularly preferably 60 to 90% by mass.
[0116] At least one of the compound having a cyclic aliphatic hydrocarbon group and an ethylenically unsaturated double bond and the compound having a fluorene ring and an ethylenically unsaturated double bond may be used alone or in combination of two or more. When two or more are used in combination, the total content is preferably within the above range.
[0117] In addition, as the above-mentioned water-resistant adhesive layer, for example, the following adhesive layer is also preferably used: as a low moisture permeability material, it is formed by a repeating unit having a structure derived from carbamate (meth) acrylate, the above-mentioned repeating unit has a branched alkyl group in the main chain, has a branched alkyl group with a branch number of 2 or more, and the repeating unit has a saturated cyclic aliphatic group, and further contains an amide structure or an ether structure in the form of clamping the branched alkyl group.
[0118] Examples of the repeating unit having a structure derived from urethane (meth)acrylate include structures represented by the following general formula (3), (4), (5) or (6).
[0119]
Chemistry 12
[0120]
[0121] In the above general formula (3), R 11 represents a branched alkyl group, R 12 represents a branched alkyl group or a saturated cyclic aliphatic group, R 13 represents a hydrogen atom or a methyl group, R 14 represents a hydrogen atom, a methyl group or an ethyl group, m represents an integer of 0 or greater, and x represents an integer of 0-3.
[0122]
Chemistry 13
[0123]
[0124] In the above general formula (4), R 11 represents a branched alkyl group, R 12 represents a branched alkyl group or a saturated cyclic aliphatic group, R 13 represents a hydrogen atom or a methyl group, R 14 represents a hydrogen atom, a methyl group or an ethyl group, n represents an integer of 1 or more, and x represents an integer of 0-3.
[0125]
Chemistry 14
[0126]
[0127] In the above general formula (5), R 11 represents a branched alkyl group, R 12 represents a branched alkyl group or a saturated cyclic aliphatic group, R 13 represents a hydrogen atom or a methyl group, R 14 represents a hydrogen atom, a methyl group or an ethyl group, m represents an integer of 0 or greater, and x represents an integer of 0-3.
[0128]
Chemistry 15
[0129]
[0130] In the above general formula (6), R 11 represents a branched alkyl group, R 12 represents a branched alkyl group or a saturated cyclic aliphatic group, R 13 represents a hydrogen atom or a methyl group, R 14 represents a hydrogen atom, a methyl group or an ethyl group, n represents an integer of 1 or more, and x represents an integer of 0-3.
[0131] It should be noted that the polymer chain (repeating unit) of the resin constituting the water-resistant adhesive layer can be determined by, for example, analyzing the adhesive layer using pyrolysis GC-MS and FT-IR. In particular, pyrolysis GC-MS can detect the monomer units contained in the adhesive layer as monomer components, and is therefore useful.
[0132] In addition, as the above-mentioned water-resistant adhesive layer, for example, the following adhesive layer is also preferably used: as a low moisture permeability material, a curable composition containing 50 to 90 mass % of a compound having three or more ethylenically unsaturated double bonds in the molecule (component A) and 10 to 40 mass % of a rosin compound (component B) having an acid value of 150 to 400 mgKOH / g is cured.
[0133] As the above-mentioned component A, i.e., the compound having three or more ethylenically unsaturated double bonds in the molecule, a (meth)acrylate compound is preferred, and examples thereof include (meth)acrylates of polyols, (meth)acrylates of ethylene oxide or propylene oxide adducts, epoxy (meth)acrylates, urethane (meth)acrylates, polyester (meth)acrylates, etc. (also referred to as trifunctional or higher multifunctional acrylate compounds). It should be noted that the above-mentioned (meth)acrylate refers to acrylate or methacrylate.
[0134] Specific examples of the trifunctional or higher polyfunctional acrylate compounds include pentaerythritol tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, EO-modified trimethylolpropane tri(meth)acrylate, PO-modified trimethylolpropane tri(meth)acrylate, EO-modified phosphoric acid tri(meth)acrylate, trimethylolethane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, polyurethane polyacrylate, polyester polyacrylate, and caprolactone-modified tri(acryloyloxyethyl)isocyanurate.
[0135] Furthermore, in addition to the above, esters of polyols and (meth) acrylic acid such as KAYARAD DPHA, DPHA-2C, PET-30, TMPTA, TPA-320, TPA-330, RP-1040, T-1420, D-310, DPCA-20, DPCA-30, DPCA-60, GPO-303 manufactured by Nippon Kayaku Co., Ltd. and V#3PA, V#400, V#36095D, V#1000, and V#1080 manufactured by Osaka Organic Chemical Industry Co., Ltd. can be mentioned.
[0136] In addition, as trifunctional or higher urethane acrylate compounds, for example, UV-1400B, UV-1700B, UV-6300B, UV-7550B, UV-7600B, UV-7605B, UV-7610B, UV-7620EA, UV-7630B, UV-7640B, UV-6630B, UV-7000B, UV-7510B, UV-7461TE, UV-3000B, UV-3200 B, UV-3210EA, UV-3310EA, UV-3310B, UV-3500BA, UV-3520TL, UV-3700B, UV-6100B, UV-6640B, UV-2000B, UV-2010B, UV-2250EA, UV-2750B (manufactured by Nippon Synthetic Chemical Co., Ltd.), UA-306H, UA-306T, UA-306I, UA-510H (manufactured by Kyoeisha Chemical Co., Ltd.), UNIDIC 17-806, 17-813, V-4030, V-4000BA (manufactured by Dainippon Ink & Chemicals Co., Ltd.), EB-1290K, EB-220, EB-5129, EB-1830, EB-4858 (manufactured by Daicel UCB), HiCoup AU-2010, AU-2020 (manufactured by Tokushiki Co., Ltd.), ARONIX M-1960 (manufactured by Toagosei Co., Ltd.), Art resin UN-3320HA, UN-3320HC, UN-3320HS, UN-904, HDP-4T, etc.
[0137] Moreover, as a trifunctional or higher-functional polyester (meth)acrylate compound, ARONIX M-8100, M-8030, M-9050 (produced by Toagosei Co., Ltd.), KRM-8307 (produced by Daicel CYTEC Co., Ltd.), etc. can also be preferably used.
[0138] Among these, it is preferred to use at least one of a (meth)acrylate compound and a urethane (meth)acrylate compound as the component (A).
[0139] The rosin compound (component B) having an acid value of 150 to 400 mgKOH / g is a material that can further reduce the moisture permeability of the adhesive layer. From the perspective of achieving both a moisture permeability reduction effect and a high pencil hardness, the acid value of the compound is 150 to 400 mgKOH / g, preferably 200 to 400 mgKOH / g, more preferably 280 to 400 mgKOH / g, and particularly preferably 320 to 400 mgKOH / g. The acid value of the component (B) is a value measured by the method described in JIS K5601-2-1.
[0140] The component (B) is preferably at least one selected from the group consisting of rosin, hydrogenated rosin (also referred to as hydrogenated rosin), and acid-modified rosin.
[0141] Examples of the rosin include unmodified rosins such as tall oil rosin, gum rosin, and wood rosin containing a resin acid such as abietic acid, levorotatory pimaric acid, palustric acid, neoabietic acid, dehydroabietic acid, or dihydroabietic acid as a main component.
[0142] The hydrogenated rosin is obtained by hydrogenating the rosin, and examples thereof include a rosin containing a high content (eg, 50% by mass or more) of tetrahydroabietic acid or the like.
[0143] Examples of the acid-modified rosin include unsaturated acid-modified rosins to which unsaturated acids such as maleic acid, fumaric acid or acrylic acid are added by a Diels-Alder addition reaction, and more specifically, examples include maleopimaric acid to which maleic acid is added, fumaric acid to which fumaric acid is added, and acrylicopimaric acid to which acrylic acid is added. Examples of the esterified rosin include alkyl esters of rosin, glycerol esters obtained by esterifying rosin with glycerol, and pentaerythritol esters obtained by esterifying rosin with pentaerythritol.
[0144] In addition, as the component (B), in addition to the above-mentioned substances, there can be mentioned Pinecrystal KR-85 (acid value: 165 to 175 mgKOH / g, softening point: 80 to 87°C), Pinecrystal KR-120 (acid value: about 320 mgKOH / g, softening point: about 120°C), Pinecrystal KR140 (acid value: 130 to 160, softening point: 130 to 150°C), Pinecrystal KR-612 (acid value: 165 to 175, softening point: 80 to 90°C), Pinecrystal KR-614 (acid value: 170 to 180, softening point: 84 to 94°C), Pinecrystal KE-604 (acid value: 230-245, softening point: 124-134°C) (all of the above are trade names, ultra-light-colored rosin derivatives, manufactured by Arakawa Chemical Industries, Ltd.), ARDYME R-95 (acid value: 158-168, softening point: 93-103°C) (all of the above are trade names, polymerized rosin, manufactured by Arakawa Chemical Industries, Ltd.), HYPALE CH (acid value: 145 or more, softening point: 65°C or more) (trade name, hydrogenated rosin, manufactured by Arakawa Chemical Industries, Ltd.), etc.
[0145] The component (B) is preferably one that has been subjected to a hydrogenation treatment after acid modification. The hydrogenation treatment can prevent the residual double bonds of the rosin compound from being oxidized in the low moisture permeability layer and coloring the film.
[0146] The softening point of the rosin compound is preferably 70 to 170° C. If the softening point of the rosin compound is 70° C. or higher, the cured layer does not soften and has excellent adhesion. If the softening point is less than 170° C., the solubility in the solvent can be maintained, and the haze of the cured layer is unlikely to increase.
[0147] In the present invention, the softening point of the rosin compound can be measured by the ring and ball method of JIS K-2531.
[0148] Regarding the content of the above-mentioned (B) component, when the total solid content of the curable composition for forming the low moisture permeable layer is set to 100 mass%, from the aspect of the significance of the reduction in moisture permeability, the content of the (B) component is preferably 10 to 35 mass%, more preferably 10 to 30 mass%, and further preferably 10 to 25 mass% relative to the total solid content.
[0149] In addition, the adhesive layer is a layer containing at least an adhesive, and examples of the adhesive include urethane-based, rubber-based, silicone-based, and acrylic-based adhesives. Among them, acrylic-based adhesives are preferred from the perspective of high heat resistance and low cost. In addition, examples of the acrylic-based adhesive include acrylic ester copolymers obtained by copolymerizing acrylic esters with other monomers.
[0150] When the adhesive layer is provided, the thickness of the adhesive layer is preferably 1 to 25 μm. If the thickness is less than 1 μm, the adhesion between the first substrate film and the second substrate film may be poor, and if the thickness exceeds 25 μm, the transparency of the laminate of the present invention may be poor.
[0151] In addition, the laminate of the present invention preferably has an optical functional layer provided on one surface of the composite base film.
[0152] The bonding strength of the composite substrate film provided with the optical functional layer is preferably 10N / 25mm or more. If it is less than 10N / 25mm, the composite substrate film is easily peeled off. The more preferred lower limit of the bonding strength is 15N / 25mm.
[0153] It should be noted that the above-mentioned adhesive strength is a value obtained as follows: using a Tensilon universal testing machine (RTC-1310A, manufactured by ORIENTEC), the two ends of the laminate cut into 25 mm × 150 mm are fixed to a clamping fixture attached to the Tensilon universal testing machine in such a manner that the length direction is the stretching direction, and the substrate film on the side where the optical functional layer is formed is stretched at a peeling speed of 300 mm / min and room temperature (23°C) in a peeling angle of 180°, and the load required for peeling the substrate film on the side where the optical functional layer is formed is measured, thereby obtaining the value. It should be noted that in the measurement of the above-mentioned adhesive strength, the object from which the substrate film on the side where the optical functional layer is formed is peeled varies according to the structure of the laminate of the present invention, for example, if the substrate film on the side where the optical functional layer is formed is the second substrate film, the object from which the second substrate film is peeled is the first substrate film, the adhesive layer or the bonding layer.
[0154] The optical functional layer may be any known layer, for example, a hard coat layer. By having the hard coat layer, the laminate of the present invention has particularly excellent strength, pencil hardness and scratch resistance.
[0155] Regarding the pencil hardness, the laminate of the present invention preferably has a hardness of 5H or more in a pencil hardness test (750 g load) specified in JIS K5600-5-4 (1999).
[0156] When measuring the pencil hardness, the laminate of the present invention is cut into a size of 5 cm×10 cm, and the obtained sample is fixed to a glass plate in a manner without folding or wrinkling using CELLOTAPE (registered trademark) manufactured by Michelbon Co., Ltd. In this state, a load of 750 g is applied to the pencil while the pencil is moved at a speed of 1 mm / second for a distance of 10 mm. The pencil hardness is the highest hardness at which the hard coating of the above sample does not produce scratches in the pencil hardness test. It should be noted that when measuring the pencil hardness, multiple pencils of different hardness are used, and each pencil is subjected to 5 pencil hardness tests. If no scratches are confirmed on the hard coating of the sample when the hard coating of the above sample is observed through the fluorescent light for more than 4 out of 5 times, it is judged that the hard coating of the sample does not produce scratches in the case of the pencil of this hardness.
[0157] In addition, regarding the above-mentioned scratch resistance, it is preferred that the laminate of the present invention is cut into a size of 5 cm×10 cm, the obtained sample is fixed to a glass plate using CELLOTAPE (registered trademark) manufactured by Michelbon in a manner without folding or wrinkling, and in this state, 1 kg / 4 cm is applied with #0000 steel wool. 2 The surface of the hard coating is rubbed back and forth 3500 times with a test length of 6 cm while being subjected to a load. Preferably, no scratches are produced in the steel wool resistance test. The presence or absence of scratches is judged as follows: a black vinyl tape (e.g., product name "Yamato vinyl tape NO200-38-21", manufactured by Yamato, 38 mm wide) is affixed to the back of a portion corresponding to the total test length of the reciprocating rubbing steel wool. When no scratches are confirmed on the surface of the hard coating when observed under a fluorescent light, it is judged that no scratches are produced on the surface of the sample. It should be noted that the scratches confirmed in a range of less than one-third of the total test length at each end are regarded as scratches at a portion where the test speed is not constant and are not counted as scratches. If scratches are produced in the steel wool test, the scratch resistance of the laminate of the present invention is sometimes insufficient. In the steel wool resistance test, it is preferred that no scratches are generated on the surface of the hard coating layer even after the steel wool is rubbed back and forth 5000 times, and it is more preferred that no scratches are generated on the surface of the hard coating layer even after the steel wool is rubbed back and forth 6500 times.
[0158] It should be noted that the laminate of the present invention preferably satisfies the above conditions regardless of whether the steel wool resistance test is performed at a low speed (50 mm / sec) or a high speed (133 mm / sec).
[0159] In addition, the laminate of the present invention preferably maintains the antifouling performance described below after the steel wool resistance test. Specifically, for example, when the contact angle of water on the surface of the hard coating layer before the steel wool resistance test is 100° or more, the contact angle of water on the surface of the hard coating layer after the steel wool resistance test is preferably 90° or more.
[0160] The laminate of the present invention can be obtained by controlling the material selection and thickness of the composite substrate film, and controlling the strength of the hard coating layer and the lamination method on the composite substrate film corresponding to the strength of the hard coating layer.
[0161] In the laminate of the present invention, the hard coat layer preferably includes a first hard coat layer provided on the composite base film side and a second hard coat layer provided on the surface of the first hard coat layer opposite to the composite base film side.
[0162] The first hard coating layer is a layer for satisfying the pencil hardness, and the Martens hardness at the center of the cross section is preferably 500 MPa or more and 1000 MPa or less. If it is less than 500 MPa, the pencil hardness of the hard coating layer becomes insufficient and sometimes cannot satisfy the pencil hardness; if it exceeds 1000 MPa, the durable folding performance of the laminate of the present invention sometimes becomes insufficient. The more preferred lower limit of the Martens hardness at the center of the cross section of the first hard coating layer is 600 MPa, and the more preferred upper limit is 950 MPa.
[0163] In addition, the second hard coating layer is a layer for satisfying the above-mentioned durable folding test, and the Martens hardness at the center of the cross section is preferably 375 MPa or more and 1500 MPa or less. If it is less than 375 MPa, the scratch resistance of the hard coating layer sometimes becomes insufficient; if it exceeds 1500 MPa, the folding resistance of the laminate of the present invention becomes insufficient, and sometimes it cannot satisfy the above-mentioned durable folding test. The more preferred lower limit of the Martens hardness at the center of the cross section of the second hard coating layer is 450 MPa, and the more preferred upper limit is 575 MPa.
[0164] In the laminate of the present invention, the Martens hardness of the first hard coating layer is preferably greater than the Martens hardness of the second hard coating layer. With such a relationship of Martens hardness, the pencil hardness of the laminate of the present invention becomes particularly good. This is because when a pencil hardness test is performed on the laminate of the present invention and a load is applied to the pencil and the pencil is pressed, the deformation of the laminate of the present invention is suppressed, and scratches and concave deformation are reduced.
[0165] Examples of a method for making the Martens hardness of the first hard coating layer higher than the Martens hardness of the second hard coating layer include a method of controlling the content of silica fine particles described below so that more silica fine particles are contained on the first hard coating layer side.
[0166] In the laminate of the present invention, the hard coating layer may be a single structure. In this case, it is preferred that the silica particles described later in the hard coating layer are concentrated on the substrate film side, that is, the presence ratio of the silica particles in the hard coating layer is larger on the substrate film side and gradually decreases on the side opposite to the substrate film side.
[0167] In addition, in this specification, "Martens hardness" means the hardness when the indenter is pressed into 500 nm by hardness measurement using the nanoindentation method.
[0168] It should be noted that in this specification, the Martens hardness determination using the nanoindentation method is performed on the laminate of the present invention cut into a sample of 30 mm × 30 mm using the "TI950TriboIndenter" manufactured by HYSITRON. That is, the Berkovich indenter (triangular pyramid) as the indenter is pressed 500 nm from the hard coating surface of the laminate of the present invention, and the residual stress is relaxed while being kept constant, and then the load is unloaded, and the maximum load after relaxation is measured, and the maximum load (Pmax (μN) and the depression area (A (nm) with a depth of 500 nm) are used to calculate the hardness of the laminate. 2 ), and the Martens hardness is calculated by Pmax / A.
[0169] In the laminate of the present invention, the first hard coat layer preferably contains a cured product of a polyfunctional (meth)acrylate as a resin component and also contains silica fine particles dispersed in the resin component.
[0170] Examples of the polyfunctional (meth)acrylate include trimethylolpropane tri(meth)acrylate, tripropylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, Tripentaerythritol octa(meth)acrylate, tetrapentaerythritol deca(meth)acrylate, isocyanurate tri(meth)acrylate, isocyanurate di(meth)acrylate, polyester tri(meth)acrylate, polyester di(meth)acrylate, bisphenol di(meth)acrylate, diglycerol tetra(meth)acrylate, adamantyl di(meth)acrylate, isobornyl di(meth)acrylate, dicyclopentane di(meth)acrylate, tricyclodecane di(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, or those modified with PO, EO, caprolactone, etc.
[0171] Among these, trifunctional to hexafunctional substances are preferred because they can well satisfy the above-mentioned Martens hardness. For example, pentaerythritol triacrylate (PETA), dipentaerythritol hexaacrylate (DPHA), pentaerythritol tetraacrylate (PETTA), dipentaerythritol pentaacrylate (DPPA), trimethylolpropane tri(meth)acrylate, tripentaerythritol octa(meth)acrylate, and tetrapentaerythritol deca(meth)acrylate are preferred.
[0172] In addition, in this specification, (meth)acrylate means acrylate and methacrylate.
[0173] The silica particles are preferably active silica particles. The active silica particles are silica particles that can form a cross-linked structure with the multifunctional (meth)acrylate. By including the active silica particles, the hardness of the first hard coating layer can be sufficiently increased, and as a result, the durable folding test can be appropriately satisfied.
[0174] The above-mentioned active silica particles preferably have reactive functional groups on their surfaces. As the reactive functional groups, for example, polymerizable unsaturated groups are suitable, more preferably photocurable unsaturated groups, and particularly preferably ionizing radiation curable unsaturated groups. Specific examples of the above-mentioned reactive functional groups include ethylenically unsaturated bonds such as (meth)acryloyl, vinyl, and allyl groups, and epoxy groups.
[0175] The activated silica fine particles are not particularly limited, and conventionally known ones can be used. Examples thereof include activated silica fine particles described in JP-A-2008-165040.
[0176] Examples of commercially available active silica fine particles include MIBK-SD, MIBK-SDMS, MIBK-SDL, and MIBK-SDZL manufactured by Nissan Chemical Industries, Ltd. and V8802 and V8803 manufactured by JGC Catalysts & Chemicals Co., Ltd.
[0177] The silica particles may be spherical silica particles, preferably irregularly shaped silica particles, or a mixture of spherical silica particles and irregularly shaped silica particles.
[0178] It should be noted that, in the present specification, the irregularly shaped silica fine particles refer to silica fine particles having a potato-like random concavo-convex shape on the surface.
[0179] The irregularly shaped silica particles have a larger surface area than spherical silica particles. Therefore, by including such irregularly shaped silica particles, the contact area with the polyfunctional (meth)acrylate and the like is increased, and the hardness (pencil hardness) of the hard coating layer can be further improved.
[0180] Whether or not the first hard coating layer is the irregularly shaped silica fine particles can be confirmed by observing a cross section of the first hard coating layer using an electron microscope.
[0181] When the above-mentioned silica particles are irregularly shaped silica particles, the average particle size of the irregularly shaped silica particles is preferably 5 to 200 nm. If it is less than 5 nm, the manufacture of the particles themselves is difficult, the particles sometimes agglomerate with each other, and it is extremely difficult to form irregular shapes. Furthermore, the dispersibility of the irregularly shaped silica particles is poor in the ink stage before the above-mentioned coating, and sometimes agglomerates. On the other hand, if the average particle size of the above-mentioned irregularly shaped silica particles exceeds 200 nm, the above-mentioned hard coating layer will form large unevenness, or the haze will increase, and other undesirable conditions will occur.
[0182] The average particle size of the irregularly shaped silica particles is the average value of the maximum value (long axis) and the minimum value (short axis) of the distance between two points on the periphery of the irregularly shaped silica particles observed in cross-sectional microscopic observation of the hard coating layer.
[0183] By controlling the size and blending amount of the silica fine particles, the hardness (Martens hardness) of the hard coating layer can be controlled, and as a result, the first hard coating layer can be formed.
[0184] For example, when forming the first hard coat layer, the silica fine particles preferably have a diameter of 5 to 200 nm and are present in an amount of 25 to 60 parts by mass based on 100 parts by mass of the resin component.
[0185] Furthermore, the second hard-coat layer preferably contains a cured product of a polyfunctional (meth)acrylate as a resin component.
[0186] Examples of the polyfunctional (meth)acrylate include the same ones as those mentioned above.
[0187] The second hard coat layer may contain, in addition to the polyfunctional (meth)acrylate as a resin component, polyfunctional urethane (meth)acrylate and / or polyfunctional epoxy (meth)acrylate.
[0188] Furthermore, the second hard coating layer may contain the silica fine particles. The content of the silica fine particles in the second hard coating layer is not particularly limited, but is preferably 0 to 50% by mass in the second hard coating layer, for example.
[0189] The above-mentioned hard coating layer, when being either the above-mentioned first hard coating layer or the second hard coating layer, may contain materials other than the above-mentioned materials within the range satisfying the above-mentioned Martens hardness. For example, the material as the resin component may contain a polymerizable monomer or a polymerizable oligomer that forms a cured product by irradiation with ionizing radiation.
[0190] Examples of the polymerizable monomer or polymerizable oligomer include a (meth)acrylate monomer having a radical polymerizable unsaturated group in the molecule, or a (meth)acrylate oligomer having a radical polymerizable unsaturated group in the molecule.
[0191] As the (meth)acrylate monomer having a free radical polymerizable unsaturated group in the above-mentioned molecule, or the (meth)acrylate oligomer having a free radical polymerizable unsaturated group in the molecule, for example, monomers or oligomers such as urethane (meth)acrylate, polyester (meth)acrylate, epoxy (meth)acrylate, melamine (meth)acrylate, polyfluoroalkyl (meth)acrylate, silicone (meth)acrylate can be cited. These polymerizable monomers or polymerizable oligomers can be used alone or in combination of two or more. Among them, polyfunctional (six or more functional) urethane (meth)acrylates with a weight average molecular weight of 1000 to 10,000 are preferred.
[0192] In order to adjust the hardness and viscosity of the composition, improve adhesion, etc., the material constituting the hard coat layer may further contain a monofunctional (meth)acrylate monomer.
[0193] Examples of the monofunctional (meth)acrylate monomer include hydroxyethyl acrylate (HEA), glycidyl methacrylate, methoxypolyethylene glycol (meth)acrylate, isostearyl (meth)acrylate, 2-acryloyloxyethyl succinate, acryloylmorpholine, N-acryloyloxyethylhexahydrophthalimide, cyclohexyl acrylate, tetrahydrofuranyl acrylate, isobornyl acrylate, phenoxyethyl acrylate, and adamantyl acrylate.
[0194] The weight average molecular weight of the polymerizable monomer is preferably less than 1,000, more preferably 200 to 800, from the viewpoint of increasing the hardness of the hard coat layer.
[0195] The weight average molecular weight of the polymerizable oligomer is preferably 1,000 to 20,000, more preferably 1,000 to 10,000, and even more preferably 2,000 to 7,000.
[0196] In addition, in this specification, the weight average molecular weight of the said polymerizable monomer and polymerizable oligomer is the weight average molecular weight measured by the GPC method in terms of polystyrene.
[0197] The hard coat layer may contain an ultraviolet absorber (UVA).
[0198] As described later, the laminate of the present invention is particularly suitable for use in mobile terminals such as foldable smartphones or tablet terminals, but such mobile terminals are mostly used outdoors, so the polarizing element arranged below the laminate of the present invention has the problem of being easily degraded by exposure to ultraviolet rays.
[0199] However, since the hard coat layer is disposed on the display screen side of the polarizing element, if the hard coat layer contains an ultraviolet absorber, the polarizing element can be appropriately prevented from being deteriorated due to exposure to ultraviolet rays.
[0200] It should be noted that the ultraviolet absorber (UVA) may be contained in the base film. In this case, the ultraviolet absorber (UVA) may not be contained in the hard coat layer.
[0201] Examples of the ultraviolet absorber include triazine ultraviolet absorbers, benzophenone ultraviolet absorbers, and benzotriazole ultraviolet absorbers.
[0202] Examples of the triazine ultraviolet absorber include 2-(2-hydroxy-4-[1-octyloxycarbonylethoxy]phenyl)-4,6-bis(4-phenylphenyl)-1,3,5-triazine, 2-[4-[(2-hydroxy-3-dodecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, and 2,4-bis[2-hydroxy-4-butoxyphenyl] -6-(2,4-dibutoxyphenyl)-1,3,5-triazine, 2-[4-[(2-hydroxy-3-tridecyloxypropyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine and 2-[4-[(2-hydroxy-3-(2'-ethyl)hexyl)oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, etc.
[0203] Examples of commercially available triazine-based ultraviolet absorbers include TINUVIN 460 and TINUVIN 477 (both manufactured by BASF), and LA-46 (manufactured by ADEKA).
[0204] Examples of the benzophenone-based ultraviolet absorber include 2-hydroxybenzophenone, 2,4-dihydroxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, hydroxymethoxybenzophenone sulfonic acid and its trihydrate, and sodium hydroxymethoxybenzophenone sulfonate.
[0205] Moreover, as a commercially available benzophenone type ultraviolet absorber, CHMASSORB81 / FL (made by BASF) etc. are mentioned, for example.
[0206] Examples of the benzotriazole ultraviolet absorber include 2-ethylhexyl-3-[3-tert-butyl-4-hydroxy-5-(5-chloro-2H-benzotriazol-2-yl)phenyl]propionate, 2-(2H-benzotriazol-2-yl)-6-(linear and side chain dodecyl)-4-methylphenol, 2-[5-chloro(2H)-benzotriazol-2-yl]-4-methyl-6-(tert-butyl)phenol, 2-(2H-benzotriazol-2-yl)-4,6-di-tert-amylphenol, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5' -di-tert-butylphenyl)benzotriazole, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3'-(3",4",5",6"-tetrahydrophthalimidomethyl)-5'-methylphenyl)benzotriazole, 2,2-methylenebis(4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol) and 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, etc.
[0207] In addition, commercially available benzotriazole-based ultraviolet absorbers include, for example, KEMISORB71D, KEMISORB79 (both manufactured by CHEMIPRO KASEI KAISHA, LTD.), JF-80, JAST-500 (both manufactured by Johoku Chemical Co., Ltd.), ULS-1933D (manufactured by Ippo Co., Ltd.), and RUVA-93 (manufactured by Otsuka Chemical Co., Ltd.).
[0208] Among them, triazine-based ultraviolet absorbers and benzotriazole-based ultraviolet absorbers are preferably used as the ultraviolet absorber.
[0209] The ultraviolet absorber is preferably one that has high solubility in the resin component constituting the hard coat layer and one that has little bleeding after the durable folding test.
[0210] The ultraviolet absorber is preferably polymerized or oligomerized.
[0211] The ultraviolet absorber is preferably a polymer or oligomer having a benzotriazole, triazine or benzophenone skeleton, and specifically, preferably one obtained by thermally copolymerizing a (meth)acrylate having a benzotriazole or benzophenone skeleton and methyl methacrylate (MMA) at an arbitrary ratio.
[0212] It should be noted that, when the laminate of the present invention is applied to OLED (organic light emitting diode), the UVA can also play a role in protecting the OLED from damage by ultraviolet rays.
[0213] The content of the ultraviolet absorber is not particularly limited, but is preferably 1 to 6 parts by mass relative to 100 parts by mass of the resin solid content of the hard coat. If it is less than 1 part by mass, the effect of the ultraviolet absorber in the hard coat cannot be fully obtained, and if it exceeds 6 parts by mass, the hard coat may be significantly colored or have reduced strength. The more preferred lower limit of the content of the ultraviolet absorber is 2 parts by mass, and the more preferred upper limit is 5 parts by mass.
[0214] The thickness of the hard coating layer is preferably 2.0 to 40.0 μm in the case of the first hard coating layer, and preferably 0.5 to 15.0 μm in the case of the second hard coating layer. If the thickness is less than the lower limit of each layer thickness, the hardness of the hard coating layer may be significantly reduced. If the thickness exceeds the upper limit of each layer thickness, it may be difficult to apply the coating solution for forming the hard coating layer, and the processability (especially, chipping resistance) may be deteriorated due to excessive thickness.
[0215] A more preferred lower limit of the thickness of the first hard coating layer is 5.0 μm, and a more preferred upper limit is 35.0 μm. A more preferred lower limit of the thickness of the second hard coating layer is 1.0 μm, and a more preferred upper limit is 10.0 μm.
[0216] The layer thickness of the hard coat layer is an average value of thicknesses at any 10 locations measured by cross-sectional electron microscope (SEM, TEM, STEM) observation.
[0217] The laminate of the present invention having the above-mentioned hard coat preferably has a transmittance of light of a wavelength of 380nm of 8% or less. If the above-mentioned transmittance exceeds 8%, when the laminate of the present invention is used in a mobile terminal, the polarizing element is exposed to ultraviolet rays and is easily degraded. The more preferred upper limit of the transmittance of light of a wavelength of 380nm of the above-mentioned hard coat is 5%. The above-mentioned transmittance can be measured using a spectrophotometer (product name "UV-3100PC", manufactured by Shimadzu Corporation), which is the arithmetic mean of the values obtained by measuring 3 times.
[0218] In addition, the haze of the hard coat layer is preferably 2.5% or less. If it exceeds 2.5%, when the laminate of the present invention is used in a mobile terminal, whitening of the display screen may become a problem. The more preferred upper limit of the haze is 1.5%, and the further preferred upper limit is 1.0%.
[0219] The haze of the hard coat layer can be achieved by, for example, adjusting the amount of the ultraviolet absorber added.
[0220] The haze can be measured using a haze meter (manufactured by Murakami Color Research Laboratory, product number: HM-150) in accordance with JIS K-7361.
[0221] It should be noted that the haze of the entire laminate of the present invention is the sum of the haze of the hard coat layer and the haze of the substrate film. When the haze of the substrate film exceeds 1%, the haze of the entire laminate of the present invention exceeds 1%.
[0222] Here, in recent years, LED (Light Emitting Diode) has been actively used as a backlight source for image display devices or touch panels such as personal computers and tablets, but the LED emits a strong light called blue light. The blue light has a wavelength of 380 to 495 nm, has a property close to ultraviolet rays, and has strong energy. Therefore, it is said that it is not absorbed by the cornea or lens and reaches the retina, causing retinal damage, eye fatigue, and adverse effects on sleep.
[0223] Therefore, when the laminate of the present invention is applied to an image display device, it is preferred that the color tone of the display screen will not be affected, and the blue light shielding property can be excellent. For the laminate of the present invention with excellent blue light shielding property, it is preferred that the spectral transmittance at a wavelength of 380nm is less than 1%, the spectral transmittance at a wavelength of 410nm is less than 10%, and the spectral transmittance at a wavelength of 440nm is more than 70%. The laminate of the present invention can fully absorb the light in the wavelength region below 410nm in the wavelength of blue light, and on the other hand, fully transmit the light above 440nm, and will not affect the color tone of the display screen and can have excellent blue light shielding property. In addition, when the laminate of the present invention with excellent blue light shielding property is applied to an organic electroluminescent (OLED) display device as an image display device, it is also effective in suppressing the degradation of OLED elements.
[0224] The light transmittance of the laminate of the present invention having excellent blue light shielding property is substantially 0% up to a wavelength of 380 nm, but gradually increases from a wavelength of 410 nm and sharply increases around a wavelength of 440 nm. Figure 2 As shown, the spectral transmittance changes in a manner describing an S-shaped curve between wavelengths of 410 nm and 440 nm.
[0225] The spectral transmittance at the above-mentioned wavelength of 380nm is more preferably less than 0.5%, further preferably less than 0.2%, the spectral transmittance at a wavelength of 410nm is more preferably less than 7%, further preferably less than 5%, and the spectral transmittance at a wavelength of 440nm is more preferably greater than 75%, further preferably greater than 80%.
[0226] It should be noted that the spectral transmittance of the laminate of the present invention is preferably less than 50% at a wavelength of 420nm. By satisfying this spectral transmittance relationship, the transmittance of the laminate of the present invention is sharply improved near a wavelength of 440nm, and extremely excellent blue light shielding properties can be obtained without affecting the color tone of the display screen.
[0227] It should be noted that Figure 2 This is a graph showing an example of the spectral transmittance of the laminated body of the present invention.
[0228] If the spectral transmittance at a wavelength of 380 nm is 1% or more, or the spectral transmittance at a wavelength of 410 nm is 10% or more, the problem caused by blue light cannot be eliminated; if the spectral transmittance at a wavelength of 440 nm is less than 70%, the color tone of the display screen of the image display device using the laminate of the present invention will be affected. It should be noted that the method for obtaining such spectral transmittance will be described later.
[0229] The spectral transmittance at the wavelength of 380 nm is more preferably less than 0.1%, the spectral transmittance at the wavelength of 410 nm is more preferably less than 7%, and the spectral transmittance at a wavelength of 440 nm is more preferably 80% or more.
[0230] The slope a of the transmission spectrum of the laminate of the present invention in the range of wavelengths of 415 to 435 nm obtained by the least square method is preferably a>2.0. If the above slope a is less than 2.0, light cannot be fully cut off in the wavelength region of blue light, such as the wavelength region of wavelengths of 415 to 435 nm, and the blue light cutting effect is sometimes weakened. In addition, the possibility of excessive cutoff of the wavelength region of blue light (wavelength 415 to 435 nm) is also considered. In this case, interference occurs in the backlight source or emission wavelength region of the image display device (for example, the light emission of OLED starting from a wavelength of 430 nm), and the possibility of adverse conditions such as hue deterioration sometimes increases. The above slope a more preferably satisfies a>1.9.
[0231] The slope a can be calculated, for example, by measuring transmittance data at the lowest five points within 1 nm before and after between 415 and 435 nm using a spectrophotometer capable of measuring in 0.5% steps (product name "UV-3100PC", manufactured by Shimadzu Corporation).
[0232] The blue light shielding rate of the laminate of the present invention is preferably 40% or more. If the blue light shielding rate is less than 40%, the above-mentioned problems caused by the blue light may not be sufficiently eliminated.
[0233] It should be noted that the blue light shielding rate is a value calculated according to JIS T 7333-2005, for example.
[0234] It should be noted that such a blue light shielding rate can be achieved, for example, by the laminate of the present invention containing a sesamol-type benzotriazole monomer described later.
[0235] The laminate of the present invention can satisfactorily satisfy the above-mentioned spectral transmittance by containing, for example, a sesamol-type benzotriazole-based monomer represented by the following general formula (1).
[0236]
Chemistry 16
[0237]
[0238] It should be noted that, in the formula, R 15 represents a hydrogen atom or a methyl group. 16 It represents a linear or branched alkylene group having 1 to 6 carbon atoms or a linear or branched oxyalkylene group having 1 to 6 carbon atoms.
[0239] The sesamol-type benzotriazole monomer is not particularly limited. Specific substance names include 2-[2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl]ethyl methacrylate, 2-[2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl]ethyl acrylate, 3-[2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl]propyl methacrylate, 3-[2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl]propyl acrylate, 4-[2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl]propyl acrylate, ,3]dioxol-5-yl)-2H-benzotriazol-5-yl]butyl methacrylate, 4-[2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl]butyl acrylate, 2-[2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yloxy]ethyl methacrylate, 2-[2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yloxy]ethyl acrylate, 2-[3-{2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl}propionyloxy]ethyl methacrylate, 2 -[3-{2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl}propionyloxy]ethyl acrylate, 4-[3-{2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl}propionyloxy]butyl methacrylate, 4-[3-{2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl}propionyloxy]butyl acrylate, 2-[3-{2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazol-5-yl}propionyloxy]ethyl methacrylate, 2-[3-{2-(6-hydroxybenzo[1,3 ]dioxol-5-yl)-2H-benzotriazole-5-yl}propionyloxy]ethyl acrylate, 2-(methacryloyloxy)ethyl 2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazole-5-carboxylate, 2-(acryloyloxy)ethyl 2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazole-5-carboxylate, 4-(methacryloyloxy)butyl 2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazole-5-carboxylate, 4-(acryloyloxy)butyl 2-(6-hydroxybenzo[1,3]dioxol-5-yl)-2H-benzotriazole-5-carboxylate, and the like.
[0240] These sesamol-type benzotriazole monomers may be used alone or in combination of two or more.
[0241] The sesamol-type benzotriazole-based monomer may be contained in the laminate of the present invention in any form as long as it satisfies the above-mentioned spectral transmittance conditions.
[0242] Specifically, for example, the laminate of the present invention may contain the above-mentioned sesamol-type benzotriazole monomer in one of the layers (for example, the above-mentioned hard coating layer), and the above-mentioned spectral transmittance condition may be satisfied by this one layer, or the function of satisfying the above-mentioned spectral transmittance condition may be shared by two or more layers.
[0243] As a configuration in which two or more layers share the function of satisfying the above-mentioned spectral transmittance condition, for example, the following configuration can be cited: the above-mentioned hard coating layer is composed of two layers, namely, a hard coating layer A and a hard coating layer B, the above-mentioned hard coating layer A contains the above-mentioned sesamol-type benzotriazole-based monomer, thereby only achieving spectral transmittance at a wavelength of 380 nm, and the above-mentioned hard coating layer B contains the above-mentioned sesamol-type benzotriazole-based monomer, thereby achieving spectral transmittance conditions at wavelengths of 410 nm and 440 nm. In addition, the above-mentioned hard coating layer may be composed of three or more layers, each of which contains the above-mentioned sesamol-type benzotriazole-based monomer, thereby satisfying the above-mentioned spectral transmittance condition.
[0244] It should be noted that the hard coat layer or the like containing the above-mentioned sesamol-type benzotriazole monomer may be present at any position in the laminate of the present invention.
[0245] In addition, the laminate of the present invention may have two or more structures having a hard coating layer on one surface of a substrate film. Specifically, the laminate of the present invention sometimes includes a structure A having a hard coating layer A on one surface of a substrate film A, and a structure B having a hard coating layer B on one surface of a substrate film B. In this case, the sesamol-type benzotriazole monomer may be contained in any of the above-mentioned structures, as long as all the structures as a whole satisfy the above-mentioned spectral transmittance conditions.
[0246] When the sesamol-type benzotriazole monomer is contained in the hard coating layer described later, for example, the sesamol-type benzotriazole monomer is preferably contained in the hard coating layer in an amount of 15 to 30 mass %. By containing the sesamol-type benzotriazole monomer in such a range, the above spectral transmittance can be satisfied.
[0247] It should be noted that the sesamol-type benzotriazole monomer may be reacted with the resin component constituting the hard coat layer to be integrally contained in the hard coat layer, or may be contained independently without reacting with the resin component constituting the hard coat layer.
[0248] As a hard coating layer that reacts with the resin component constituting the hard coating layer and integrally contains a sesamol-type benzotriazole monomer, specifically, for example, a hard coating layer formed as follows: when the sesamol-type benzotriazole monomer is set as A, methyl methacrylate (MMA) is set as B, and an ultraviolet absorber (such as "RUVA93" manufactured by Otsuka Chemical Co., Ltd.) is set as C, these A, B, and C are reacted and combined in an acrylic acid or acrylate polymer, and formed using a hard coating composition containing 90 parts of a polymer with a mixing ratio of A being 10 to 55 parts by mass and 10 parts of PETA. The laminate of the present invention having the hard coating layer obtained in this way can satisfy the above-mentioned spectral transmittance and has excellent blue light shielding performance.
[0249] The hard coat layer may contain other components as necessary, such as a lubricant, a plasticizer, a filler, an anti-blocking agent, a crosslinking agent, a light stabilizer, an antioxidant, and a colorant such as a dye or pigment other than the blue dye.
[0250] In addition, the laminate of the present invention can be formed with another hard coating (hereinafter also referred to as back hard coating) on the surface of the opposite side of the substrate film provided with the hard coating (first hard coating and second hard coating). As the back hard coating, for example, the same layer as the hard coating can be cited.
[0251] In addition, as the above-mentioned back hard coating layer, it is preferable to have a back hard coating layer (1) and / or a back hard coating layer (2).
[0252] Examples of the back hard coat layer (1) and the back hard coat layer (2) include layers having the same composition and thickness as the first hard coat layer or the second hard coat layer.
[0253] That is, in the case where the laminate of the present invention has the above-mentioned back hard coating layer, as the back hard coating layer, there can be cited: a structure having a back hard coating layer (1) that is the same as the above-mentioned first hard coating layer; a structure having a back hard coating layer (1) that is the same as the above-mentioned second hard coating layer; a structure in which a back hard coating layer (1) that is the same as the above-mentioned first hard coating layer and a back hard coating layer (2) that is the same as the above-mentioned second hard coating layer are stacked in sequence from the substrate film side; a structure in which a back hard coating layer (1) that is the same as the above-mentioned second hard coating layer and a back hard coating layer (2) that is the same as the above-mentioned first hard coating layer are stacked in sequence from the substrate film side.
[0254] In addition, when the laminated body of the present invention is mounted on a touch panel, since the above-mentioned back hard coating layer is arranged on the surface opposite to the outermost surface side, the antifouling property described later is not required.
[0255] Furthermore, the laminate of the present invention preferably has antifouling properties. Such antifouling properties can be obtained, for example, by making the hard coat layer contain an antifouling agent.
[0256] The contact angle between the surface of the hard coating layer containing the above-mentioned antifouling agent and water is preferably 100° or more. In the laminate of the present invention just after manufacture, the contact angle between the surface of the hard coating layer and water is more preferably 105° or more. The contact angle between the surface of the hard coating layer and water after the steel wool resistance test under the above-mentioned condition 3 is preferably 90° or more, more preferably 103° or more.
[0257] The antifouling agent is preferably concentrated on the outermost surface side of the hard coating layer. When the antifouling agent is uniformly contained in the hard coating layer, in order to impart sufficient antifouling performance, it is necessary to increase the amount of addition, which may cause the film strength of the hard coating layer to decrease. It should be noted that when the hard coating layer has the first hard coating layer and the second hard coating layer, the antifouling agent is preferably concentrated on the outermost surface side of the second hard coating layer disposed on the outermost surface side.
[0258] As a method for making the above-mentioned antifouling agent concentrated on the outermost surface side of the hard coating layer, for example, the following methods can be mentioned: when forming the hard coating layer, before drying and curing a coating film formed using the hard coating composition described later, heat is applied to the above-mentioned coating film to reduce the viscosity of the resin component contained in the coating film, thereby improving fluidity, and making the above-mentioned antifouling agent concentrated on the outermost surface side; a method in which an antifouling agent with low surface tension is selected and used, and the above-mentioned antifouling agent is floated on the surface of the coating film without applying heat when drying the above-mentioned coating film, and then the coating film is cured, thereby making the above-mentioned antifouling agent concentrated on the outermost surface side.
[0259] The antifouling agent is not particularly limited, and examples thereof include silicone-based antifouling agents, fluorine-based antifouling agents, and silicone-based and fluorine-based antifouling agents, each of which may be used alone or in combination. In addition, the antifouling agent may be an acrylic antifouling agent.
[0260] Specific examples of the antifouling agent include fluorine-containing antifouling agents (trade name: OPTOOL DAC, manufactured by Daikin Industries, Ltd.) and the like.
[0261] The content of the antifouling agent is preferably 0.01 to 3.0 parts by weight relative to 100 parts by weight of the resin material. If it is less than 0.01 parts by weight, sufficient antifouling properties may not be imparted to the hard coat layer, while if it exceeds 3.0 parts by weight, the hardness of the hard coat layer may decrease.
[0262] The antifouling agent preferably has a weight average molecular weight of 5,000 or less, and is preferably a compound having one or more, more preferably two or more, reactive functional groups in order to improve the durability of the antifouling performance.
[0263] In addition, the said weight average molecular weight can be calculated|required by polystyrene conversion by gel permeation chromatography (GPC).
[0264] In addition, the antifouling agent having the above-mentioned reactive functional group has good antifouling performance continuity (durability), wherein the hard coating layer containing the above-mentioned fluorine-containing antifouling agent is difficult to be attached with fingerprints (not easy to be conspicuous) and has good wiping properties. In addition, the surface tension of the above-mentioned hard coating layer forming composition during coating can be reduced, so the leveling property is good and the appearance of the formed hard coating layer is good.
[0265] In addition, the hard coating layer containing the silicone-based antifouling agent has good sliding properties and excellent steel wool resistance.
[0266] For a touch panel equipped with the laminate of the present invention containing such a silicone-based antifouling agent in the hard coating layer, the sliding when touched with a finger or a pen becomes better, and the touch becomes better. In addition, the hard coating layer is also difficult to be attached with fingerprints (not easy to be conspicuous), and the wiping property is also good. In addition, the surface tension of the composition (composition for hard coating layer) when forming the hard coating layer can be reduced during coating, so the leveling property is good and the appearance of the formed hard coating layer is good.
[0267] In addition, the antifouling agent having the above-mentioned reactive functional group can be obtained as a commercial product. As commercial products other than the above-mentioned, for example, as a silicone-containing antifouling agent, for example, SUA1900L10 (manufactured by Shin-Nakamura Chemical Co., Ltd.), SUA1900L6 (manufactured by Shin-Nakamura Chemical Co., Ltd.), Ebecryl1360 (manufactured by Daicel CYTEC), UT3971 (manufactured by Nippon Gosei Co., Ltd.), BYKUV3500 (manufactured by BYK Chemical Co., Ltd.), BYKUV3510 (manufactured by BYK Chemical Co., Ltd.), BYKUV3570 (manufactured by BYK Chemical Co., Ltd.), X22-164E, X22-174BX, X22-2426, KBM503, KBM5103 (manufactured by Shin-Etsu Chemical Co., Ltd.), TEGO-RAD2250, TEGO-RAD2300, TEGO-RAD2200N, TEGO-RAD2010, TEGO-RAD2500, TEGO-RAD2600, TEGO-RAD2700 (manufactured by Evonik Japan), MEGAFACE RS854 (manufactured by DIC Corporation), etc.
[0268] Examples of the fluorine-containing antifouling agent include OPTOOL DAC, OPTOOL DSX (manufactured by Daikin Industries, Ltd.), MEGAFACE RS71, MEGAFACE RS74 (manufactured by DIC Corporation), LINC152EPA, LINC151EPA, LINC182UA (manufactured by Kyoeisha Chemical Co., Ltd.), Ftergent 650A, Ftergent 601AD, and Ftergent 602.
[0269] Examples of the fluorine-containing and silicone-containing antifouling agent having a reactive functional group include MEGAFACE RS851, MEGAFACE RS852, MEGAFACE RS853, and MEGAFACE RS854 (manufactured by DIC Corporation), Opstar TU2225, Opstar TU2224 (manufactured by JSR Corporation), and X71-1203M (manufactured by Shin-Etsu Chemical Co., Ltd.).
[0270] The hard coat layer can be formed using, for example, a hard coat layer composition to which the resin component, active silica fine particles, an ultraviolet absorber, or other components are added.
[0271] The hard coat composition may contain a solvent as necessary.
[0272] Examples of the solvent include alcohols (e.g., methanol, ethanol, propanol, isopropanol, n-butanol, sec-butanol, tert-butanol, benzyl alcohol, PGME, ethylene glycol, and diacetone alcohol), ketones (e.g., acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclopentanone, cyclohexanone, heptanone, diisobutyl ketone, diethyl ketone, and diacetone alcohol), esters (methyl acetate, ethyl acetate, butyl acetate, n-propyl acetate, isopropyl acetate, methyl formate, and PGMEA), aliphatic hydrocarbons (e.g., hexane and cyclohexane), halogenated hydrocarbons (e.g., dichloromethane, chloroform, and carbon tetrachloride), aromatic hydrocarbons (e.g., benzene, toluene, and xylene), amides (e.g., dimethylformamide, dimethylacetamide, and n-methylpyrrolidone), ethers (e.g., diethyl ether, dioxane, and tetrahydrofuran), ether alcohols (e.g., 1-methoxy-2-propanol), and carbonates (dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate). These solvents may be used alone or in combination of two or more.
[0273] Among them, as the solvent, methyl isobutyl ketone and methyl ethyl ketone are preferred from the viewpoint of being able to dissolve or disperse the resin components such as the polymerizable monomer and / or polymerizable oligomer and other additives and appropriately apply the hard coat composition.
[0274] The above-mentioned hard coating composition preferably has a total solid content of 25 to 55%. If it is less than 25%, residual solvent may remain or whitening may occur. If it exceeds 55%, the viscosity of the hard coating composition increases, the coating property decreases, and unevenness or stripes may sometimes occur on the surface. The above-mentioned solid content is more preferably 35 to 50%.
[0275] Examples of a method for producing the laminate of the present invention using the hard coat composition include a method in which the hard coat composition is applied to one surface of a composite substrate film to form a coating layer, and the coating layer is dried and then cured.
[0276] As a method for forming a coating layer by coating the above-mentioned hard coating composition on one surface of a substrate film, various well-known methods such as spin coating, dipping, spraying, die coating, rod coating, roller coating, meniscus coating, flexographic printing, screen printing, and droplet coating can be cited.
[0277] The method for drying the coating film is not particularly limited, but the coating film is usually dried at 30 to 120° C. for 10 to 120 seconds.
[0278] The coating film may be cured by any known method selected appropriately according to the composition of the hard coat composition, etc. For example, if the hard coat composition is an ultraviolet curable composition, the coating layer may be cured by irradiating ultraviolet rays.
[0279] It should be noted that, in the case where the hard coating layer has the first hard coating layer and the second hard coating layer, the first hard coating layer composition prepared for forming the first hard coating layer is applied to the substrate film, and the formed coating layer is dried and semi-cured. By forming the second hard coating layer described later in a semi-cured state without completely curing the coating layer, the adhesion between the first hard coating layer and the second hard coating layer becomes extremely excellent. As a method for semi-curing the coating layer, for example, 100 mJ / cm 2 The method of irradiating the dried coating film with ultraviolet rays is as follows.
[0280] The second hard coating composition prepared for forming the second hard coating is applied to the semi-cured first hard coating, and after the formed coating is dried, the coating is completely cured, so that the second hard coating can be formed on the first hard coating. It should be noted that by completely curing the coating using the second hard coating composition, the steel wool resistance of the surface of the hard coating (second hard coating) becomes excellent. As a method for completely curing the coating of the second hard coating composition, for example, a method for curing the coating by ultraviolet irradiation under a nitrogen atmosphere (oxygen concentration is preferably 500ppm or less, more preferably 200ppm or less, and further preferably 100ppm or less) can be cited. In addition, by increasing the crosslinking degree (reaction rate) of the side opposite to the first hard coating side of the second hard coating as the outermost surface, the steel wool resistance can also be improved.
[0281] It should be noted that when the first hard coating layer and the second hard coating layer are formed by the above method, in order to obtain a sufficiently cured hard coating layer (the first hard coating layer and the second hard coating layer), the total ultraviolet irradiation amount is preferably 150 mJ / cm 2 above.
[0282] In the present invention, the hard coat layer may be a hard coat layer formed by a conventionally known thermosetting sol-gel method.
[0283] It should be noted that the above-mentioned thermosetting sol-gel method is generally known as the following method, that is, for example, an alkoxysilane compound having an epoxy group is hydrolyzed to form a gel that loses fluidity through a condensation reaction, and the gel is heated to obtain an oxide. In addition, for example, it can also be a method of hydrolyzing an alkoxysilane compound and causing it to undergo a condensation reaction to obtain an oxide; a method of heating an alkoxysilane compound having an isocyanate group and causing it to undergo a condensation reaction to obtain an oxide; and a method of further mixing the alkoxysilane compound and a compound having an isocyanate group in an arbitrary proportion, hydrolyzing them, and causing them to undergo a condensation reaction.
[0284] The alkoxysilane compound having an epoxy group is not particularly limited as long as it has at least one epoxy group and one hydrolyzable silicon group in each molecule, and examples thereof include γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltriethoxysilane.
[0285] The hydrolyzate of the alkoxysilane compound having an epoxy group can be obtained by dissolving the alkoxysilane compound having an epoxy group in an appropriate solvent for hydrolysis. Examples of the solvent used include alcohols such as methyl ethyl ketone, isopropanol, methanol, ethanol, methyl isobutyl ketone, ethyl acetate, butyl acetate, ketones, esters, halogenated hydrocarbons, aromatic hydrocarbons such as toluene and xylene, or mixtures thereof. Among them, methyl ethyl ketone is preferred from the perspective of having a drying speed suitable for forming a coating.
[0286] When the hydrolysis is performed, a catalyst may be used as necessary. The catalyst used is not particularly limited, and a known acid catalyst or base catalyst may be used.
[0287] Examples of the acid catalyst include organic acids such as acetic acid, chloroacetic acid, citric acid, benzoic acid, dimethylmalonic acid, formic acid, propionic acid, glutaric acid, glycolic acid, malonic acid, maleic acid, toluenesulfonic acid, and oxalic acid; inorganic acids such as hydrochloric acid, nitric acid, and silane halides; and acidic sol-like fillers such as acidic colloidal silica and titanium dioxide sol. These may be used alone or in combination of two or more.
[0288] Examples of the alkaline catalyst include aqueous solutions of hydroxides of alkali metals or alkaline earth metals such as sodium hydroxide and calcium hydroxide, aqueous ammonia, and aqueous solutions of amines. Among them, hydrochloric acid or acetic acid, which have high catalytic reaction efficiency, is preferably used.
[0289] The hydrolyzate of the alkoxysilane compound having an epoxy group can be obtained by dissolving the alkoxysilane compound having an epoxy group in an appropriate solvent for hydrolysis. Examples of the solvent used include alcohols such as methyl ethyl ketone, isopropanol, methanol, ethanol, methyl isobutyl ketone, ethyl acetate, butyl acetate, ketones, esters, halogenated hydrocarbons, aromatic hydrocarbons such as toluene and xylene, or mixtures thereof. Among them, methyl ethyl ketone is preferred from the perspective of having a drying speed suitable for forming a coating.
[0290] The alkoxysilane compound having an isocyanate group is not particularly limited, and examples thereof include 3-isocyanatepropyltriethoxysilane, 3-isocyanatepropyltrimethoxysilane, and 2-isocyanateethyltri-n-propoxysilane.
[0291] The compound having an isocyanate group is not particularly limited, and examples thereof include toluene diisocyanate (TDI), 3,3'-benzylene-4,4'-isocyanate, diphenylmethane 4,4'-diisocyanate (MDI), triphenylmethane p,p',p"-triisocyanate (TM), 2,4-benzylene dimer (TT), naphthalene-1,5-diisocyanate, tri(4-phenylisocyanate)thiophosphate, crude (MDI), TDI trimer, dicyclohexamethane 4,4'-diisocyanate (H MDI), hydrogenated TDI (HTDI), meta-xylylene diisocyanate (XDI), hexahydro-meta-xylylene diisocyanate (HXDI), hexamethylene diisocyanate, trimethylpropane-1-methyl-2-isocyano-4-carbamate, polymethylene polyphenyl isocyanate, 3,3'-dimethoxy 4,4'-diphenyl diisocyanate, diphenyl ether 2,4,1'-triisocyanate, meta-xylylene diisocyanate (MXDI), polymethylene polyphenyl isocyanate (PAPI), etc.
[0292] The laminated body of the present invention preferably further has a conductive layer containing a conductive fibrous filler.
[0293] The conductive fibrous filler of the present invention preferably has a fiber diameter of 200 nm or less and a fiber length of 1 μm or more.
[0294] If the fiber diameter exceeds 200 nm, the manufactured conductive layer may have an increased haze value or insufficient light transmission performance. From the perspective of the conductivity of the conductive layer, the preferred lower limit of the fiber diameter of the conductive fibrous filler is 10 nm, and the more preferred range of the fiber diameter is 15 to 180 nm.
[0295] In addition, if the fiber length of the above-mentioned conductive fibrous filler is less than 1 μm, it is sometimes impossible to form a conductive layer with sufficient conductive performance, and agglomeration will occur, which may cause an increase in the haze value or a decrease in light transmittance. Therefore, the preferred upper limit of the above-mentioned fiber length is 500 μm, and the more preferred range of the above-mentioned fiber length is 3 to 300 μm, and the further preferred range is 10 to 30 μm.
[0296] It should be noted that the fiber diameter and fiber length of the above-mentioned conductive fibrous filler can be measured at 1000 to 500,000 times magnification using an electron microscope such as SEM, STEM, or TEM, and the fiber diameter and fiber length can be obtained as the average value of 10 points.
[0297] As the conductive fibrous filler, for example, at least one selected from the group consisting of conductive carbon fibers, metal fibers, and metal-coated synthetic fibers is preferred.
[0298] Examples of the conductive carbon fibers include vapor grown carbon fibers (VGCF), carbon nanotubes, wire cups, wire walls, etc. These conductive carbon fibers may be used alone or in combination of two or more.
[0299] As the metal fibers, for example, fibers produced by a wire drawing method or a cutting method of thinning and elongating stainless steel, iron, gold, silver, aluminum, nickel, titanium, etc. can be used. One or more types of such metal fibers can be used.
[0300] Examples of the metal-coated synthetic fibers include acrylic fibers coated with gold, silver, aluminum, nickel, titanium, etc. Such metal-coated synthetic fibers may be used alone or in combination of two or more.
[0301] The content of the conductive fibrous filler in the conductive layer is preferably 20 to 3000 parts by mass, for example, relative to 100 parts by mass of the resin component constituting the conductive layer. If it is less than 20 parts by mass, a conductive layer with sufficient conductive performance may not be formed sometimes. If it exceeds 3000 parts by mass, the conductive laminate of the present invention may have an increased haze or insufficient light transmission performance. In addition, the amount of the conductive fibrous filler entering the contact points through the binder resin increases, thereby deteriorating the conduction of the conductive layer, and the conductive laminate of the present invention may not obtain the target resistance value sometimes. The more preferred lower limit of the content of the conductive fibrous filler is 50 parts by mass, and the more preferred upper limit is 1000 parts by mass.
[0302] In addition, the resin component of the conductive layer is not particularly limited, and conventionally known materials can be mentioned.
[0303] In addition, as other conductive agents other than the above-mentioned conductive fibrous fillers, for example, there can be mentioned: quaternary ammonium salts, pyridinium salts, various cationic compounds having cationic groups such as primary to tertiary amino groups, anionic compounds having anionic groups such as sulfonate groups, sulfate ester groups, phosphate ester groups, phosphonate groups, etc., amphoteric compounds such as amino acids and aminosulfate esters, non-ionic compounds such as amino alcohols, glycerols, and polyethylene glycols, organic metal compounds such as tin and titanium alcohol salts, and metal chelates such as their acetylacetonates, etc.; and compounds obtained by high-molecular-weighting the above-mentioned compounds; and monomers or oligomers having tertiary amino groups, quaternary ammonium groups, or metal chelate moieties and being polymerizable by ionizing radiation; or polymerizable compounds such as organic metal compounds such as coupling agents having polymerizable functional groups that are polymerizable by ionizing radiation, etc.
[0304] The content of the other conductive agent is preferably 1 to 50 parts by mass relative to 100 parts by mass of the resin component constituting the conductive layer. If it is less than 1 part by mass, a conductive layer having sufficient conductive performance may not be formed, and if it exceeds 50 parts by mass, the conductive laminate of the present invention may have increased haze or insufficient light transmission performance.
[0305] Furthermore, as the conductive agent, for example, conductive fine particles may be used.
[0306] As specific examples of the above-mentioned conductive particles, conductive particles composed of metal oxides can be cited. As such metal oxides, for example, ZnO (refractive index 1.90, the numerical value in brackets below represents the refractive index), CeO2 (1.95), Sb2O5 (1.71), SnO2 (1.997), indium tin oxide (1.95) often referred to as ITO, In2O3 (2.00), Al2O3 (1.63), antimony-doped tin oxide (abbreviated as: ATO, 2.0), aluminum-doped zinc oxide (abbreviated as: AZO, 2.0), etc. can be cited. The average particle size of the above-mentioned conductive particles is preferably 0.1nm to 0.1μm. By being within this range, when the above-mentioned conductive particles are dispersed in the raw material of the resin component constituting the conductive layer, a composition that can form a highly transparent film with basically no haze and good total light transmittance is obtained.
[0307] The content of the conductive fine particles is preferably 10 to 400 parts by mass relative to 100 parts by mass of the resin component constituting the conductive layer. If it is less than 10 parts by mass, a conductive layer having sufficient conductive performance may not be formed, and if it exceeds 400 parts by mass, the conductive laminate of the present invention may have increased haze or insufficient light transmission performance.
[0308] As the above-mentioned conductive agent, for example, high molecular weight conductive agents such as polyparaphenylene of an aromatic conjugated system, polypyrrole and polythiophene of a heterocyclic conjugated system, polyacetylene of an aliphatic conjugated system, polyaniline of a heteroatom-containing conjugated system, polyphenylene vinylene of a mixed conjugated system, a multi-chain conjugated system having two or more conjugated chains in a molecule, and a conductive composite of a polymer in which the above-mentioned conjugated polymer chains are grafted or block-copolymerized onto a saturated polymer can also be used.
[0309] The conductive layer may contain refractive index adjusting particles.
[0310] Examples of the refractive index adjustment particles include high refractive index fine particles and low refractive index fine particles.
[0311] The high refractive index particles are not particularly limited, and examples thereof include: particles composed of high refractive index materials such as resins with high refractive indexes and their precursors containing aromatic rings, sulfur atoms or bromine atoms in resin materials such as aromatic polyimide resins, epoxy resins, (meth) acrylic resins, polyester resins and urethane resins; or metal oxide particles or metal alkoxide particles, etc.
[0312] The low refractive index particles are not particularly limited, and examples thereof include particles made of low refractive index materials such as resins with low refractive index containing fluorine atoms in resin materials such as epoxy resins, (meth) acrylic resins, polyester resins and urethane resins, and their precursors; or magnesium fluoride particles, hollow or porous particles (organic, inorganic), etc.
[0313] The laminate of the present invention has antistatic properties by having the conductive layer.
[0314] When a polyimide film is used as the composite substrate film, the composite substrate film is easily charged because fluorine atoms are contained in the molecule. Therefore, by providing the laminate of the present invention with antistatic properties, a polyimide film that is easily charged can be appropriately used.
[0315] The antistatic property may be imparted by forming the conductive layer, or may be imparted by incorporating the conductive agent (antistatic agent) into any layer constituting the laminate of the present invention without separately providing a conductive layer.
[0316] When the antistatic agent is used, the content thereof is preferably 1 to 30% by mass based on the total mass of the total solid content.
[0317] In addition, the laminate of the present invention preferably has an antireflection layer when used as a surface material of an image display device. By having an antireflection layer, surface reflection when the laminate of the present invention is used as a surface material of an image display device can be suppressed, and a display screen with excellent display quality can be formed.
[0318] Examples of the antireflection layer include a structure in which a high refractive index layer and a low refractive index layer are stacked.
[0319] The high refractive index layer is not particularly limited, and examples thereof include a structure including a known binder resin and the high refractive index fine particles.
[0320] The low refractive index layer is not particularly limited, and may be, for example, a layer containing a known binder resin and the low refractive index fine particles.
[0321] The laminate of the present invention has the above-mentioned structure, and thus has extremely excellent hardness and folding performance, and is also excellent in transparency and surface smoothness.
[0322] Such a laminate of the present invention preferably has a layer thickness (total thickness) of 30 to 1000 μm. If the thickness of the laminate of the present invention is less than 30 μm, physical properties such as impact resistance sometimes differ, and if it exceeds 1000 μm, the above-mentioned folding performance may not be satisfied. A more preferred upper limit of the thickness of the laminate of the present invention is 500 μm, and a further preferred upper limit is 300 μm. If the optical properties are also considered, the most preferred upper limit of the thickness of the laminate of the present invention is 150 μm.
[0323] In addition, the laminate of the present invention can be used not only as a surface protective film for image display devices such as liquid crystal display devices, in the same manner as a hard coat film having a conventionally known hard coat layer, but can also be used as a surface protective film for curved display screens or products having curved surfaces, or a surface protective film for foldable parts. Furthermore, the laminate of the present invention is smooth and has excellent transparency, and therefore can be appropriately used either on the side closer to the display screen than the light-emitting layer of the image display device or on the side opposite to the display screen.
[0324] Among them, the laminate of the present invention has extremely excellent foldability and is therefore suitable for use as a surface protection film for foldable parts.
[0325] In addition, when the laminate of the present invention is used as a member for a touch panel, it is preferable that it has antimicrobial properties. The method for imparting the antimicrobial properties is not particularly limited, and conventionally known methods can be used.
[0326] In addition, in the case of a member for a touch panel, the laminate of the present invention preferably has a blue light cutoff property obtained by a conventionally known method. It should be noted that the blue light refers to light with a wavelength of 385 to 495 nm.
[0327] As the foldable component, there is no particular limitation as long as it is a component with a foldable structure, and examples thereof include foldable image display devices such as foldable smartphones or foldable touch panels, foldable (electronic) photo albums, etc. It should be noted that an image display device formed using the laminate of the present invention is also one of the present invention.
[0328] The folding position in the member having a foldable structure may be one, or two or more, and the folding direction may be arbitrarily determined as required.
[0329] Effects of the Invention
[0330] Since the laminated body of the present invention is formed by the above-mentioned structure, it has extremely excellent hardness and durable folding performance.
[0331] Therefore, the hard coating film of the present invention has excellent transparency and smoothness. Thus, in addition to being a surface protective film similar to those with existing hard coatings, it can also be suitably used as a surface protective film for products with curved surfaces, or as a surface material or any internal part of a foldable component such as a foldable image display device, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0332] Figure 1 It is a cross-sectional view schematically showing a durability folding test.
[0333] Figure 2 It is a graph showing an example of the spectral transmittance of the laminate of the present invention. DETAILED DESCRIPTION OF THE INVENTION
[0334] Hereinafter, examples and comparative examples will be given to more specifically explain the present invention, but the present invention is not limited to these examples and comparative examples.
[0335] It should be noted that in this text, "parts" or "%" are based on mass unless otherwise specified.
[0336]
Chemical Formula 17
[0337]
[0338]
Chemical Formula 18
[0339]
[0340]
Chemical Formula 19
[0341]
[0342]
Chemical Formula 20
[0343]
[0344]
Chemical Formula 21
[0345]
[0346]
Chemical Formula 22
[0347]
[0348] (Example 1)
[0349] As a first substrate film, a polyimide film having a polyimide skeleton represented by the above formula (A) with a thickness of 30 μm was prepared, and an adhesive layer composition AA with the following composition was applied on one surface of the first substrate film to form a coating film. The formed coating film was heated at 70° C. for 1 minute to evaporate the solvent in the coating film, and then an ultraviolet irradiation device (manufactured by Fusion UV Systems Japan, light source H bulb) was used in the air with a cumulative light intensity of 100 mJ / cm 2 The coating film was semi-cured by irradiating ultraviolet rays in a manner to form an adhesive layer with a thickness of 10 μm.
[0350] Next, a polyimide film having a polyimide skeleton represented by the above formula (A) was placed as a second base film with an adhesion thickness of 30 μm on the above adhesive layer to produce a composite base film.
[0351] Next, a hard coating composition 1 having the following composition was applied to the second substrate film of the composite substrate film to form a coating film. The formed coating film was heated at 70° for 1 minute to evaporate the solvent in the coating film, and then irradiated with an ultraviolet irradiation device (manufactured by Fusion UV Systems Japan, light source H bulb) in air at a cumulative light intensity of 100 mJ / cm 2 The coating film was semi-cured by irradiating ultraviolet rays in a manner to form a first hard coating layer with a thickness of 3 μm.
[0352] Next, a hard coating composition a with the following composition was applied on the first hard coating layer to form a coating film. Next, the formed coating film was heated at 70° for 1 minute to evaporate the solvent in the coating film, and an ultraviolet irradiation device (manufactured by Fusion UV Systems Japan, light source H bulb) was used to irradiate the coating film at an oxygen concentration of 200 ppm or less and a cumulative light intensity of 200 mJ / cm 2 The coating film was completely cured by irradiating with ultraviolet rays in a manner to form a second hard coating layer with a thickness of 2 μm, thereby producing a laminate.
[0353] (Adhesive layer composition AA)
[0354] Acryloylmorpholine (ACMO, manufactured by KOHJIN Film & Chemicals Co., Ltd.) 100 parts by mass
[0355] Lucirin TPO (manufactured by BASF Japan) 4 parts by mass
[0356] Solvent (MIBK) 20 parts by mass
[0357] (Hard Coat Composition 1)
[0358] 25 parts by mass of a mixture of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate (M403, manufactured by Toagosei Co., Ltd.)
[0359] Dipentaerythritol EO-modified hexaacrylate (A-DPH-6E, manufactured by Shin-Nakamura Chemical Co., Ltd.) 25 parts by mass
[0360] Irregular-shaped silica particles (average particle size 25 nm, manufactured by JGC Catalysts & Chemicals Co., Ltd.) 50 parts by mass (based on solid content)
[0361] Photopolymerization initiator (Irg184, manufactured by BASF Japan) 4 parts by mass
[0362] Fluorine-based leveling agent (F568, manufactured by DIC Corporation) 0.2 parts by mass (based on solid content)
[0363] Solvent (MIBK) 150 parts by mass
[0364] (Hard Coating Composition a)
[0365] Urethane acrylate (UX5000, manufactured by Nippon Kayaku Co., Ltd.) 25 parts by mass
[0366] 50 parts by mass of a mixture of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate (M403, manufactured by Toagosei Co., Ltd.)
[0367] Multifunctional acrylate polymer (ACRIT 8KX-012C, manufactured by TAISEI FINE CHEMICAL Co., Ltd.) 25 parts by mass (based on solid content)
[0368] Antifouling agent (BYKUV3500, manufactured by BYK Chemicals) 1.5 parts by mass (based on solid content)
[0369] Photopolymerization initiator (Irg184, manufactured by BASF Japan) 4 parts by mass
[0370] Solvent (MIBK) 150 parts by mass
[0371] (Example 2)
[0372] A laminate was produced in the same manner as in Example 1 except that a 30 μm thick polyimide film having a polyimide skeleton represented by the above formula (B) was used as the first base film and the second base film, respectively, instead of the 30 μm thick polyimide film having a polyimide skeleton represented by the above formula (A).
[0373] (Example 3)
[0374] A laminate was produced in the same manner as in Example 1 except that a 30 μm thick polyimide film having a polyimide skeleton represented by the above formula (C) was used as the first base film and the second base film, respectively, instead of the 30 μm thick polyimide film having a polyimide skeleton represented by the above formula (A).
[0375] (Example 4)
[0376] A laminate was produced in the same manner as in Example 1 except that a 30 μm thick polyimide film having a polyimide skeleton represented by the above formula (D) was used as the first base film and the second base film, respectively, instead of the 30 μm thick polyimide film having a polyimide skeleton represented by the above formula (A).
[0377] (Example 5)
[0378] A laminate was produced in the same manner as in Example 1 except that a 30 μm thick polyimide film having a polyimide skeleton represented by the above formula (E) was used as the first base film and the second base film, respectively, instead of the 30 μm thick polyimide film having a polyimide skeleton represented by the above formula (A).
[0379] (Example 6)
[0380] A laminate was produced in the same manner as in Example 1 except that a 30 μm thick polyimide film having a polyimide skeleton represented by the above formula (F) was used as the first base film and the second base film, respectively, instead of the 30 μm thick polyimide film having a polyimide skeleton represented by the above formula (A).
[0381] (Example 7)
[0382] A laminate was produced in the same manner as in Example 1 except that a 30 μm thick polyimide film having a polyimide skeleton represented by the above formula (F) was used as the first base film instead of the 30 μm thick polyimide film having a polyimide skeleton represented by the above formula (A).
[0383] (Example 8)
[0384] A laminate was produced in the same manner as in Example 1 except that a 50 μm thick PET film (manufactured by Toray Industries, Inc.) was used as the first base film instead of the 30 μm thick polyimide film having a polyimide skeleton represented by the above formula (A).
[0385] (Example 9)
[0386] A laminate was produced in the same manner as in Example 1 except that a 40 μm-thick acrylic film (manufactured by Okura Industries) was used as the first base film instead of the 30 μm-thick polyimide film having a polyimide skeleton represented by the above formula (A).
[0387] (Example 10)
[0388] A laminate was produced in the same manner as in Example 1 except that a polyimide film having a thickness of 50 μm and having a polyimide skeleton represented by the above formula (A) was used as the first base film and the second base film, respectively.
[0389] (Example 11)
[0390] A laminate was produced in the same manner as in Example 1 except that a polyimide film having a thickness of 100 μm and having a polyimide skeleton represented by the above formula (A) was used as the first base film and the second base film, respectively.
[0391] (Example 12)
[0392] A laminate was produced in the same manner as in Example 1 except that the thickness of the adhesive layer was changed to 7 μm.
[0393] (Example 13)
[0394] A laminate was produced in the same manner as in Example 1 except that the thickness of the adhesive layer was changed to 5 μm.
[0395] (Example 14)
[0396] A laminate was produced in the same manner as in Example 1 except that the thickness of the adhesive layer was changed to 3 μm.
[0397] (Example 15)
[0398] A laminated body was produced in the same manner as in Example 1 except that a hard coat composition 2 having the following composition was used instead of the hard coat composition 1.
[0399] (Hard Coat Composition 2)
[0400] 25 parts by mass of a mixture of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate (M403, manufactured by Toagosei Co., Ltd.)
[0401] Hexafunctional acrylate (MF001, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) 25 parts by mass
[0402] Irregular-shaped silica particles (average particle size 25 nm, manufactured by JGC Catalysts & Chemicals Co., Ltd.) 50 parts by mass (based on solid content)
[0403] Fluorine-based leveling agent (F568, manufactured by DIC Corporation) 0.2 parts by weight (based on solid content)
[0404] Photopolymerization initiator (Irg184, manufactured by BASF Japan) 4 parts by weight
[0405] Solvent (MIBK) 150 parts by mass
[0406] (Example 16)
[0407] A laminated body was produced in the same manner as in Example 1 except that a hard coat composition 3 having the following composition was used instead of the hard coat composition 1.
[0408] (Hard Coat Composition 3)
[0409] A mixture of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate (M403, manufactured by Toagosei Co., Ltd.) 35 parts by mass
[0410] Dipentaerythritol EO-modified hexaacrylate (A-DPH-6E, manufactured by Shin-Nakamura Chemical Co., Ltd.) 35 parts by mass
[0411] 30 parts by mass of irregular silicon dioxide fine particles (average particle size 25 nm, manufactured by JGC Catalysts & Chemicals Co., Ltd.) (based on solid content)
[0412] Photopolymerization initiator (Irg184, manufactured by BASF Japan) 4 parts by weight
[0413] Fluorine-based leveling agent (F568, manufactured by DIC Corporation) 0.2 parts by weight (based on solid content)
[0414] Solvent (MIBK) 150 parts by mass
[0415] (Example 17)
[0416] A laminated body was produced in the same manner as in Example 1 except that a hard coat composition 4 having the following composition was used instead of the hard coat composition 1.
[0417] (Hard Coat Composition 4)
[0418] 25 parts by mass of a mixture of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate (M403, manufactured by Toagosei Co., Ltd.)
[0419] Dipentaerythritol EO-modified hexaacrylate (A-DPH-6E, manufactured by Shin-Nakamura Chemical Co., Ltd.) 25 parts by mass
[0420] Solid silica fine particles (average particle size 12 nm, MIBKSD, manufactured by Nissan Chemical Co., Ltd.) 50 parts by mass (based on solid content)
[0421] Fluorine-based leveling agent (F568, manufactured by DIC Corporation) 0.2 parts by weight (based on solid content)
[0422] Photopolymerization initiator (Irg184, manufactured by BASF Japan) 4 parts by weight
[0423] Solvent (MIBK) 150 parts by mass
[0424] (Example 18)
[0425] A laminate was produced in the same manner as in Example 1 except that a hard coat composition b having the following composition was used instead of the hard coat composition a.
[0426] (Hard coating composition b)
[0427] Urethane acrylate (UX5000, manufactured by Nippon Kayaku Co., Ltd.) 50 parts by mass
[0428] 50 parts by mass of a mixture of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate (M403, manufactured by Toagosei Co., Ltd.)
[0429] Antifouling agent (BYKUV3500, manufactured by BYK Chemicals) 1.5 parts by mass (based on solid content)
[0430] Photopolymerization initiator (Irg184, manufactured by BASF Japan) 4 parts by weight
[0431] Solvent (MIBK) 150 parts by mass
[0432] (Example 19)
[0433] A laminate was produced in the same manner as in Example 1 except that a hard coat composition c having the following composition was used instead of the hard coat composition a.
[0434] (Hard Coat Composition c)
[0435] Urethane acrylate (KRM8452, manufactured by Daicel-Allnex) 100 parts by mass
[0436] Antifouling agent (TEGO-RAD2600, manufactured by Evonik Japan) 1.5 parts by mass (based on solid content)
[0437] Photopolymerization initiator (Irg184, manufactured by BASF Japan) 4 parts by weight
[0438] Solvent (MIBK) 150 parts by mass
[0439] (Example 20)
[0440] A laminate was produced in the same manner as in Example 1 except that a hard coat composition d having the following composition was used instead of the hard coat composition a.
[0441] (Hard Coat Composition d)
[0442] Urethane acrylate (UV7600B, manufactured by Nippon Synthetic Chemical Co., Ltd.) 50 parts by mass
[0443] Pentaerythritol triacrylate (M306, manufactured by Toagosei Co., Ltd.) 50 parts by mass
[0444] Antifouling agent (X71-1203M) (manufactured by Shin-Etsu Chemical Co., Ltd.) 0.5 parts by mass (based on solid content)
[0445] Photopolymerization initiator (Irg184, manufactured by BASF Japan) 4 parts by weight
[0446] Solvent (MIBK) 150 parts by mass
[0447] (Example 21)
[0448] A laminate was produced in the same manner as in Example 1 except that an adhesive layer composition BB having the following composition was used instead of the adhesive layer composition AA.
[0449] (Adhesive layer composition BB)
[0450] Isobornyl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., IBXA) 100 parts by mass
[0451] Lucirin TPO (manufactured by BASF Japan) 4 parts by mass
[0452] MIBK 20 parts by mass
[0453] (Example 22)
[0454] A laminate was produced in the same manner as in Example 1 except that an adhesive layer composition CC having the following composition was used instead of the adhesive layer composition AA.
[0455] (Adhesive layer composition CC)
[0456] Phenoxyethyl acrylate (LIGHT ACRYLATE PO-A, manufactured by Kyoeisha Chemical Co., Ltd.) 100 parts by mass
[0457] Lucirin TPO (manufactured by BASF Japan) 4 parts by mass
[0458] MIBK 20 parts by mass
[0459] (Example 23)
[0460] A laminate was produced in the same manner as in Example 1 except that an adhesive layer composition DD having the following composition was used instead of the adhesive layer composition AA.
[0461] (Adhesive layer composition DD)
[0462] Acryloylmorpholine (ACMO, manufactured by KOHJIN Film & Chemicals) 60 parts by mass
[0463] Pentaerythritol triacrylate (PET30, manufactured by Nippon Kayaku Co., Ltd.) 40 parts by mass
[0464] Lucirin TPO (manufactured by BASF Japan) 4 parts by mass
[0465] MIBK 20 parts by mass
[0466] (Example 24)
[0467] A laminate was produced in the same manner as in Example 1 except that an adhesive layer composition EE having the following composition was used instead of the adhesive layer composition AA.
[0468] (Adhesive layer composition EE)
[0469] Acryloylmorpholine (ACMO, manufactured by KOHJIN Film & Chemicals) 60 parts by mass
[0470] Dipentaerythritol hexaacrylate (made by Nippon Kayaku Co., Ltd., DPHA) 40 parts by mass
[0471] Lucirin TPO (manufactured by BASF Japan) 4 parts by mass
[0472] MIBK 20 parts by mass
[0473] (Example 25)
[0474] A laminate was produced in the same manner as in Example 1 except that the thickness of the first hard coat layer was changed to 5 μm.
[0475] (Example 26)
[0476] A laminate was produced in the same manner as in Example 1 except that the thickness of the first hard coat layer was changed to 10 μm.
[0477] (Example 27)
[0478] A laminate was produced in the same manner as in Example 1 except that the thickness of the first hard coat layer was changed to 2 μm.
[0479] (Example 28)
[0480] A laminate was produced in the same manner as in Example 1 except that the thickness of the second hard coat layer was changed to 5 μm.
[0481] (Example 29)
[0482] A laminate was produced in the same manner as in Example 1 except that the thickness of the second hard coat layer was changed to 0.5 μm.
[0483] (Example 30)
[0484] A laminate was produced in the same manner as in Example 1 except that 3 parts by mass (in terms of solid content) of cobalt particles (blue pigment, manufactured by CIKasei Corporation) were added to the hard coat composition 1.
[0485] (Example 31)
[0486] A laminate was produced in the same manner as in Example 1 except that a water-resistant adhesive layer having a thickness of 5 μm was formed on both surfaces of the adhesive layer by the following method.
[0487] A water-resistant adhesive layer composition of the following composition was applied to one surface of the adhesive layer formed by the same method as in Example 1 to form a coating film. The formed coating film was heated at 70° C. for 1 minute to evaporate the solvent in the coating film, and then irradiated with an ultraviolet irradiation device (manufactured by Fusion UV Systems Japan, light source H bulb) in air at a cumulative light intensity of 100 mJ / cm 2 The coating film was semi-cured by irradiating ultraviolet rays to form a water-resistant adhesive layer with a thickness of 5 μm, and then on the other side of the adhesive layer, a water-resistant adhesive layer with a thickness of 5 μm was formed under the same conditions using a water-resistant adhesive layer composition having the following composition.
[0488] (Composition for water-resistant adhesive layer)
[0489] Tricyclodecane dimethanol diacrylate (A-DCP, manufactured by Shin-Nakamura Chemical Co., Ltd.) 100 parts by mass
[0490] Fluorine-based leveling agent (F568, manufactured by DIC Corporation) 0.2 parts by mass (based on solid content)
[0491] Photopolymerization initiator (Irg184, manufactured by BASF Japan) 4 parts by mass
[0492] Solvent (MIBK) 150 parts by mass
[0493] (Comparative Example 1)
[0494] As a base film, a polyimide film having a thickness of 30 μm and having a polyimide skeleton represented by the above formula (A) was prepared, and a first hard coating layer and a second hard coating layer were provided on one surface of the base film in the same manner as in Example 1 to produce a laminate.
[0495] (Comparative Example 2)
[0496] A laminate was produced in the same manner as in Comparative Example 1 except that a 50 μm thick PET film (manufactured by Toray Industries, Inc.) was used as the first base film instead of the 30 μm thick polyimide film having a polyimide skeleton represented by the above formula (A).
[0497] (Comparative Example 3)
[0498] A laminate was produced in the same manner as in Comparative Example 1 except that a 40 μm thick acrylic film (manufactured by Okura Industries) was used as the first base film instead of the 30 μm thick polyimide film having a polyimide skeleton represented by the above formula (A).
[0499] (Comparative Example 4)
[0500] A laminate was produced in the same manner as in Comparative Example 1 except that a 25 μm thick TAC film (manufactured by Fujifilm Corporation) was used as the first base film instead of the 30 μm thick polyimide film having a polyimide skeleton represented by the above formula (A).
[0501] (Comparative Example 5)
[0502] A laminate was produced in the same manner as in Example 1 except that a 50 μm-thick PET film (manufactured by Toray Industries, Inc.) was used as the first base film and the second base film instead of the 30 μm-thick polyimide film having a polyimide skeleton represented by the above formula (A).
[0503] (Comparative Example 6)
[0504] A laminate was produced in the same manner as in Example 1 except that a 40 μm-thick acrylic film (manufactured by Okura Industries) was used as the first base film and the second base film instead of the 30 μm-thick polyimide film having a polyimide skeleton represented by the above formula (A).
[0505] (Comparative Example 7)
[0506] A laminate was produced in the same manner as in Example 1 except that a 25 μm-thick TAC film (manufactured by Fujifilm Corporation) was used as the first base film and the second base film instead of the 30 μm-thick polyimide film having a polyimide skeleton represented by the above formula (A).
[0507] (Reference Example 1)
[0508] A laminate was produced in the same manner as in Example 1 except that the thickness of the adhesive layer was changed to 30 μm.
[0509] (Reference Example 2)
[0510] A laminate was produced in the same manner as in Example 1 except that a polyimide film having a thickness of 200 μm and having a polyimide skeleton represented by the above formula (A) was used as the first base film.
[0511] (Reference Example 3)
[0512] A laminate was produced in the same manner as in Example 1 except that a polyimide film having a thickness of 200 μm and having a polyimide skeleton represented by the above formula (A) was used as the first base film and the second base film.
[0513] (Reference Example 4)
[0514] A laminate was produced in the same manner as in Example 1 except that a 25 μm-thick adhesive layer (trade name: PD-R5, manufactured by PANAC) was used instead of the adhesive layer.
[0515] The laminates obtained in Examples, Comparative Examples, and Reference Examples were subjected to the following evaluations.
[0516] (Folding test)
[0517] The laminates of the examples, comparative examples and reference examples (hereinafter, the surface on which the hard coating layer is formed is referred to as the front surface, and the surface on the opposite side is referred to as the back surface) were cut into rectangles of 30 mm × 100 mm. The short sides (30 mm) of the prepared samples were fixed to a durability tester (DLDMLH-FS, manufactured by YUASA SYSTEM Co., Ltd.) by fixing parts, as shown in FIG. Figure 1 As shown in (c), the sample is installed so that the minimum spacing between the two opposing sides is 3 mm (the outer diameter of the bent portion is 3.0 mm), and a test is performed in which the surface of the sample having the hard coating layer is folded 180° 100,000 times (the test is performed by folding the sample with the back side being the outer side) (durable folding test).
[0518] After that, a new sample was replaced, and the surface of the sample with the hard coating layer was folded 180° in the same manner with the interval between the two opposing sides being 3 mm, and placed in an environment of 60°C and 90% for 12 hours (folding retention test), and the presence of cracks or breakage in the bent portion was evaluated according to the following criteria.
[0519] ○: No cracks or breaks in the bent part
[0520] ×: Cracks or breaks occurred in the bent part
[0521] (Impact resistance)
[0522] A soda-lime glass having a thickness of 0.7 mm was placed on a flat table, and the laminated bodies of the examples, comparative examples and reference examples were cut into 5 cm × 15 cm sizes to obtain samples. The obtained samples were fixed to the soda-lime glass using CELLOTAPE (registered trademark) manufactured by Michelbon in a manner that there were no folds or wrinkles, and the weight was adjusted to 1.5 kg. An iron ball was dropped from a height of 30 cm. This test was conducted with N=3 and evaluated based on the following criteria.
[0523] ○: No cracks occurred in the sample and the soda-lime glass in all three times (the drop position was changed each time)
[0524] ×: The sample or soda-lime glass has cracks
[0525] (Pencil hardness)
[0526] The pencil hardness of the laminated bodies of the examples and comparative examples was measured based on JIS K5600-5-4 (1999). When measuring the pencil hardness, the laminated bodies of the examples, comparative examples and reference examples were cut into a size of 5 cm × 10 cm, and the obtained samples were fixed to a glass plate in a manner without folding or wrinkling using CELLOTAPE (registered trademark) manufactured by Michibond Co., Ltd. In this state, a load of 750 g was applied to the pencil while the pencil was moved a distance of 10 mm at a speed of 1 mm / second. The pencil hardness is the highest hardness at which the hard coating of the sample does not produce scratches in the pencil hardness test. It should be noted that when measuring the pencil hardness, multiple pencils of different hardness were used, and each pencil was subjected to 5 pencil hardness tests. If no scratches were confirmed on the hard coating of the sample when the hard coating of the sample was observed through the fluorescent light for more than 4 out of 5 times, it was judged that the hard coating of the sample did not produce scratches in the case of the pencil of that hardness.
[0527] (Adhesion Strength)
[0528] Using a Tensilon universal testing machine (RTC-1310A, manufactured by ORIENTEC), the laminated bodies of the examples, comparative examples and reference examples were cut into pieces of 25 mm × 150 mm, and the two ends of the obtained sample were fixed to a clamping fixture attached to the Tensilon universal testing machine in such a manner that the length direction was the stretching direction. The substrate film on the side having the hard coating layer formed thereon was stretched in a peeling angle of 180° at a peeling speed of 300 mm / min and room temperature (23°C), and the load required for peeling was measured, thereby obtaining the result.
[0529] (Yellow Index)
[0530] The yellowness index of the laminated bodies of the examples, comparative examples and reference examples was measured by using a spectrophotometer (product name "UV-3100PC", manufactured by Shimadzu Corporation, light source: tungsten lamp and deuterium lamp) on a sample cut into a size of 5 cm × 10 cm. The chromaticity tristimulus values X, Y, and Z were calculated from the measured values according to the calculation formula described in JIS Z8722: 2009, and the tristimulus values X, Y, and Z were calculated according to the calculation formula described in ASTM D1925: 1962. The yellowness index is the arithmetic mean of the values obtained by three measurements.
[0531] (Surface uniformity)
[0532] The maximum height Rz of the profile was measured for an arbitrary 5 μm×5 μm region of the laminated bodies of Examples, Comparative Examples, and Reference Examples using a scanning probe microscope (SPM-9600, manufactured by Shimadzu Corporation) in accordance with JIS B0601:2001.
[0533] (Young's modulus)
[0534] A Tensilon universal testing machine (RTC-1310A, manufactured by ORIENTEC) was used. The two ends of the laminate cut into 2 mm × 50 mm were fixed to a clamping fixture attached to the Tensilon universal testing machine in such a way that the length direction was the tensile direction. The measured values of the elongation and load of the laminate when stretched at a test speed of 25 mm / min were converted into strain and stress, and the slope of the straight line connecting the stress when the strain was 0.5% and the stress when the strain was 1% was obtained.
[0535]
Table 1
[0536]
[0537] As shown in Table 1, the laminates of Examples 1 to 31 were excellent in durable folding performance, folding retention performance, impact resistance, pencil hardness, and color tone change. In particular, the laminate of Example 30 contained cobalt particles in the hard coat layer, thereby suppressing the yellowing of the base film, resulting in a lower YI, and the laminate of Example 31 had extremely excellent water resistance because water-resistant adhesive layers were provided on both sides of the adhesive layer.
[0538] On the other hand, the laminates of Comparative Examples 1 to 4 were poor in the results of the durable folding test and the impact resistance peel strength because the substrate film was not a composite substrate film. In addition, the laminates of Comparative Examples 5 to 7 that did not use a specific substrate film had poor pencil hardness, and the laminate of Comparative Example 6 had poor impact resistance and surface smoothness.
[0539] In addition, the laminate of Reference Example 1 has a thick adhesive layer and poor folding retention performance. The laminate of Reference Example 2 has a large YI because the first substrate film is 200 μm thick. The laminate of Reference Example 3, in which the substrate film is 200 μm thick, has a large Rz value and poor surface smoothness in addition to a large YI. In addition, the laminate of Reference Example 4 has a small Young's modulus value because the first substrate film and the second substrate film are laminated via an adhesive layer.
[0540] Industrial Applicability
[0541] The laminate of the present invention can be suitably used as a surface material of a foldable image display device.
[0542] Explanation of symbols
[0543] 10 Laminated body of the present invention
[0544] 11Fixed part
[0545] 12 bending parts.
Claims
1. A laminated body used in an image display device, the laminated body comprising a composite substrate film having a structure in which a first substrate film and a second substrate film are laminated, The laminate is characterized in that At least one of the first substrate film and the second substrate film is a polyimide film, a polyamideimide film, or an aromatic polyamide film, A first hard coating layer provided on the composite substrate film side and a second hard coating layer provided on the surface of the first hard coating layer opposite to the composite substrate film side, wherein the first hard coating layer contains silica particles dispersed in a resin component and the second hard coating layer contains a multifunctional urethane (meth) acrylate. The Martens hardness of the center of the cross section of the first hard coating layer is 500 MPa to 1000 MPa, and the Martens hardness of the center of the cross section of the second hard coating layer is 375 MPa to 1500 MPa. When the laminate was repeatedly subjected to a test of folding the laminate 180 degrees so that the interval between two opposing sides was 3 mm 100,000 times, no crack or break occurred in the laminate. 2 . The laminate according to claim 1 , which has a yellowness index of 15 or less. The laminate according to claim 1 or 2, which has a Young's modulus of 3 GPa or more.
4. The laminate according to claim 1 or 2, wherein: The maximum height Rz of the profile of any region of 5 μm×5 μm on the surface of the composite base film is 0.1 μm or less.
5. The laminate according to claim 1 or 2, wherein: When the laminate was folded at 180° so that the interval between two opposing sides was 3 mm and kept at a temperature of 60° C. and a humidity of 90% for 12 hours, the laminate did not crack or break.
6. The laminate according to claim 1 or 2, wherein: An optical functional layer is provided on one surface of a composite base film, and the composite base film provided with the optical functional layer has an adhesive strength of 10 N / 25 mm or more.
7. The laminate according to claim 1 or 2, wherein: When an iron ball having a weight of 100 g and a diameter of 30 mm was dropped from a height of 30 cm on one surface of the laminate, the laminate did not generate cracks.
8. An image display device, characterized in that: The laminate comprises the laminate according to claim 1 or 2.
Citation Information
Patent Citations
Curable resin composition for hard coat layer and hard coat film
JP2008165040A
Hard coat film
JP2014186210A
Hard coat film, curable resin composition for hard coat layer, and method for producing hard coat film
JP2014238614A
Isolation region, semiconductor device and manufacturing method thereof
WO2012000316A1
Coating composition, method for modifying matrix surface, and product coated by the coating composition
CN102241899A